A hybrid attention-based deep learning framework for high-accuracy microplastic detection and monitoring in water environments - Xinyu Zhang; Cheng-Hao Yu; Rong Fu; Leixin Ouyang; Ziliang Zhang; Lina Pu; Mark Ming-Cheng Cheng (Water Research, 2027)

Experimental study of seepage and water-rock heat transfer in granite fracture under chemical action - Ruotao Liu; Guan Rong; Bowen Li; Zhongjie Yu; Huqi Zhang; Qinyan Qiu (European Journal of Environmental and Civil Engineering, 2026)

Exploring the potential mechanisms of the Prunus mume-Prunella vulgaris herb pair in treating endometrial polyps based on network pharmacology and molecular docking - Wen Yan Zhang; Yuan Yuan; Li Fan; Guang Rong Huang; Shu Yu Pan; Jing Xiao (Molecular Genetics and Genomics, 2026)

First report of Fusarium weifangense, F. puerense and F. asiaticum causing leaf spot disease on Morus alba L. in China - Mei Lei; Rong Xiao; Lixia Zhang; Yu Tian; Zhongrong Zheng; Zehui Zhao; Tingting Zhao; Zhu Li; Haixia Ding (Crop Protection, 2026)

Reconstruction of the Cretaceous palaeo-plateau in South China: Insights from geochemical thermobarometry and isostasy modelling - Hanqiao Zheng; Junfeng Gong; Rong Yang; Ruohong Jiao; Junqing He; Fengqi Zhang; Hongdan Deng; Jiakang Huang; Zhiquan Yu; Yunlong Wang; Hanlin Chen; Shufeng Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A natural Nlscarlet insertion underlies the orange-eye phenotype and facilitates efficient multiple-sgRNA genome editing in Nilaparvata lugens - Wen-Nan Ye; Rong-Yu Chen; Qi Xing; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

Regulating proton back-diffusion to enhance lithium sulfate conversion in bipolar membrane electrodialysis - Rong Zhang; Lingyun Wang; Xin Wang; Zhe Yu; Wenkai Wang; Ming Tan; Yang Liu; Yang Zhang (Desalination, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

Bioinspired orientation-regulated conductive hydrogels with hierarchical lamellar architecture for synergistic mechanical and electrical robustness - Tianhao Yu; Chao Rong; Ting Su; Shijia Wan; Bowei Zhang; Yabin Yan; Fu-Zhen Xuan (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Unraveling the discrepancies in absorption and assimilation mechanisms between ammonium and nitrate in Ulva pertusa: Implication by physiological responses, transcriptomics and molecular docking - Huaqiu Zhang; Yu Liu; Guoguang Wang; Haiyue Chen; Guangzhi Rong; Haixia Wang (Aquaculture, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

Carbon cloth-mediated direct interspecies electron transfer effect on the intensification mechanism of high-load codigestion dynamic membrane bioreactors - Bao-Shan Xing; Yi-Fan Wu; Yi Zhang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Surface-engineered Au@Pt nanoparticles-based colorimetric/fluorescent dual-mode three-channel sensor array: Discrimination of light aroma-type Baijiu with variable qualities - Yukun Yang; Jian Liu; Rong Guo; Baoqing Bai; Tao Bo; Jinhua Zhang; Ligang Yu; Huilin Liu; Ying Zhang; Shuo Wang (Food Chemistry, 2026)

Integrated network toxicology, transcriptomics, and metabolomics revealed the potential mechanisms of aluminum-induced testicular injury - Siyu Liao; Liqing Huang; Yusi Zhou; Xin Zhang; Shaofeng Huang; Linjun Yu; Shiman Zhu; Wei Chen; Rong Wang; Haimei Qin (Food and Chemical Toxicology, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Construction and application of an antifouling transistor-based cytosensor for detection of CTCs - Rong Zou; Huiling Yan; Lei Wang; Yu Chen; Caiyuan Liao; Bowen Zhang; Gang Chang; Ping Wang; Hanping He (Chemical Engineering Journal, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Decadal Resampling Reveals Widespread Increases in Soil Microbial Diversity Associated With Nitrogen Deposition - Yi Fan; Yiheng Tao; Bin Hua; Paul Kardol; Yakov Kuzyakov; Shuang Pang; Yi Wu; Tingling Li; Wei Yang; Honghui Wu; Anton A. Goncharov; Anastasia Yu. Korotkevich; et al. (Global Change Biology, 2026)
Simulated manipulation experiments, such as nitrogen addition to mimic atmospheric nitrogen deposition, are widely used in global change research. However, experimental manipulations may differ from real‐world environmental change in their intensity, duration, and co‐occurrence, leaving long‐term changes in soil microbial communities and soil health insufficiently understood. To address this gap, we resampled soils from 38 forest and grassland ecosystems across eastern China in 2009 and 2019 and assessed microbial taxonomic and functional diversity using shotgun metagenomics. Microbial diversity increased by 17% over the decade, accompanied by clear shifts in community composition. Among the environmental variables considered, nitrogen deposition (~19 kg nitrogen ha −1 year −1 across ecosystems) was the strongest predictor of changes in seven of 12 microbial community metrics. Larger nitrogen deposition was also associated with increased relative abundances of nitrogen‐cycling genes and reduced spatial turnover in microbial community composition. These effects were consistent with a potential alleviation of nitrogen limitation and weakening of deterministic community assembly, although these mechanisms could not be directly established. In addition, increases in genes associated with carbon degradation and phosphorus cycling, together with declines in the relative abundances of pathogens, antibiotic resistance genes, and DNA viruses, coincided with the raise of the composite soil health index. Our findings demonstrate widespread decadal increases in soil microbial diversity and soil health across eastern China, with nitrogen deposition emerging as their strongest environmental factor. These results highlight that microbial responses to long‐term ambient environmental change can differ markedly from responses inferred from short‐term or high‐intensity manipulation experiments.

Dysregulation of xenobiotic metabolism and mitochondrial dysfunction exacerbate acetaminophen-induced hepatotoxicity in human antigen R-deficient male mice - Natalie Eppler; Elizabeth Jones; Forkan Ahamed; Naren Raja; Jephte Y. Akakpo; Margitta Lebofsky; Lily He; Ira Vats; Priyanka Ghosh; Yifan Yu; Kaitlyn Thomas; Colin McCoin; et al. (Toxicology, 2026)

Regulatory role of the keystone taxa Dokdonella in bacterial network stability under grazing disturbance in alpine meadows - Hainian Lu; Jiaoyang Du; Yongli Xie; Yu Zou; Xiujin Zhang; Dingan Gao; Xiaohui Wu; Chaokun Wang; Rong Wang (Rhizosphere, 2026)

Inoculation with phosphate-solubilizing bacteria reduce the transport of cadmium in Brassica napus L. by reshaping phosphate-solubilizing microbes in rhizosphere - Xiao Chen Zhang; Tong Yu Feng; Xiu Rong Tao; Lu Chen Wang; Jing Wen Kong; Yi Yao Mai; Yang Chen; Qing Guo; Long Guo; Chuan Jun Dai; Min Zhao (Rhizosphere, 2026)

Field resistance monitoring and nAChR α6 target validation support spinetoram as a candidate insecticide for rotation in Nilaparvata lugens resistance management - Wen-Nan Ye; Qi Xing; Rong-Yu Chen; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Surface interception and transport of 14C-labeled polystyrene nanoplastics by benthic marine organisms - Wenwen Song; Dongxu Li; Jun Zhang; Ziyun Huang; Hongjie Zhang; Changhong Liu; Aijun Miao; Yu Su; Rong Ji (Marine Environmental Research, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Additives-induced alteration of PVC pyrolysis pathways and emission profiles - Siying Ran; Haoran Yu; Rong Cao; Ningbo Geng; Yuan Gao; Haijun Zhang; Lidong Wu; Jiping Chen (Journal of Hazardous Materials, 2026)

Peptidomics-driven screening of ACE inhibitory peptides from cheese: Molecular mechanisms and modulation of endothelial function in HUVECs - Ying Xu; Dongyang Li; Huan Wang; Yu Zhang; Liangyan Rong; Ruren Li (Food Bioscience, 2026)

Denitrification-enhanced anaerobic digestion for stable synergy of hydrolysis and methanogenesis of N, N-dimethylformamide by nitrate addition: Delayed stimulation effect for successful enrichment of functional microorganisms - Junjie Zhou; Zhihao Shi; Tao Zhang; Yao Xu; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; Zhe Kong (Environmental Research, 2026)

The Study on the Biological Characteristics of Photobacterium damselae subsp. damselae Affected by the Deletion of the Iron Uptake System Genes tonB1 and tonB2 - Hua Jiang; Yufei Ji; Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Xiaojun Rong; Aijun Ma; Shuyi Li; Zheng Zhang (Fishes, 2026)
Photobacterium damselae subsp. damselae (PDD), a marine fish pathogen, has an unclear contribution of tonB genes to iron acquisition and pathogenicity. ΔtonB1-PDD and ΔtonB2-PDD mutants as well as their complemented strains were generated via homologous recombination from the virulent strain PDD1605. Growth was evaluated by monitoring OD600 with viable-count calibration, intracellular iron was measured using a colorimetric assay, biofilm was detected by crystal violet staining, transcription was analyzed through qRT-PCR, and pathogenicity was assessed via an 8-day intramuscular challenge in black rockfish (Sebastes schlegelii). Under iron limitation induced by 100 μM 2,2′-dipyridyl, the maximum density decreased from 4.51 × 108 CFU/mL in wild-type (WT-PDD) to 4.00 × 108 and 3.64 × 108 CFU/mL in ΔtonB1-PDD and ΔtonB2-PDD respectively, and was largely restored after complementation. The intracellular iron content declined from 3.75 × 10−4 ± 4.00 × 10−6 nmol/106 cells in WT-PDD to 3.13 × 10−4 ± 1.05 × 10−5 nmol/106 cells in ΔtonB1-PDD and 2.55 × 10−4 ± 2.00 × 10−5 nmol/106 cells in ΔtonB2-PDD. Compared with WT-PDD, biofilm formation was reduced by 22.1% in ΔtonB1-PDD and by 24.8% in ΔtonB2-PDD. Deletion of tonB2 induced mild yet statistically significant transcriptional alterations in multiple iron acquisition and virulence-related genes, while colony morphology, swarming motility, hemolysis, phospholipase activity, biochemical traits, and antimicrobial susceptibility remained unchanged. In the high-dose challenge assay, WT-PDD caused 100% mortality within 2 days, whereas ΔtonB1-PDD and ΔtonB2-PDD caused 17/20 and 18/20 deaths respectively; all infected groups reached 100% mortality by day 3. In the low-dose challenge assay, WT-PDD, ΔtonB1-PDD, and ΔtonB2-PDD caused 12/20, 12/20, and 13/20 deaths by day 2, with cumulative mortalities reaching 80%, 70%, and 80% by day 8, respectively. Kaplan–Meier analysis detected no significant differences among the survival curves at either challenge dose. These findings suggest that tonB1 and tonB2 play roles in iron acquisition, low-iron adaptation, and biofilm formation, with tonB2 deletion exerting greater effects on growth and intracellular iron accumulation under iron-limited conditions.

Assessing impacts of vertical mixing parameterizations on ENSO simulation in a ROMS-based hybrid coupled model - Yinnan Li; Yang Yu; Maonan Chen; Chuan Gao; Hongna Wang; Liu Yang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Extracellular polymeric substances: overlooked contributors to soil organic carbon persistence - Yichao Wu; Yuwei Yi; Minsu Kim; Samuel Bickel; Ming Zhang; Ke Dai; Chunhui Gao; Chenchen Qu; Chuisi Kong; Mengxi Feng; Ke-Qing Xiao; Hans-Curt Flemming; et al. (Soil Biology and Biochemistry, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

China could simultaneously increase wheat yield and nitrogen use efficiency under the temperature rise of 1 ℃ through optimal crop managements - Kaiyuan Gong; Shuoqiu Ding; Yadong Luo; Yinghua Zhang; Xiao Wang; Fengying Duan; Xia Li; Liangbing Rong; Zhihao He; Hao Feng; Qiang Yu; Wenbin Zhou; et al. (European Journal of Agronomy, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Biocrust-forming mosses mediate bacterial community assembly in response to aridity across northern China - Fang Du; Xiaoying Rong; Xiaobing Zhou; Shen Yu; Zachary T. Aanderud; Yuanming Zhang (Applied Soil Ecology, 2026)

Sedimentary DNA and Fossil Archives Reveal Long‐Term Phytoplankton Shifts and Their Biogeochemical Influence in a Subtropical Lake - Yu Zhao; Jianan Zheng; Meifang Zhong; Wenxiu Zheng; Bo Qin; Kexin Zhu; Chenxue Zhang; Yanjie Zhao; Enlou Zhang; Eric Capo; Rong Wang (Molecular Ecology, 2026)
Understanding long‐term phytoplankton community dynamics is essential for assessing ecological resilience and informing lake management under global change. However, centennial‐scale patterns of phytoplankton dynamics remain poorly resolved due to the limited taxonomic resolution of traditional fossil‐based paleoecological approaches. In this study, a combination of sedimentary DNA (sedDNA) and subfossil diatom analysis was used to investigate changes in the phytoplankton community over the past two centuries and associated sedimentary biogeochemical responses in Lake Xiliang, a subtropical lake in the Yangtze River Basin, China. The sedDNA data captured major shifts in both eukaryotic and cyanobacterial communities, revealing distinct ecological phases linked to human activities and regional climate warming. Under near‐natural conditions with minimal human disturbance, phytoplankton communities typically exhibit low diversity and are characterized by oligotrophic taxa such as xanthophytes and Gyrosigma . After the 1930s, increases in epiphytic Staurosira and declines in tychoplanktonic Aulacoseira suggest reduced river–lake connectivity and weaker water‐column turbulence following the construction of the Jinshui Sluice, likely facilitating macrophyte expansion. In recent decades, intensified anthropogenic pressures combined with regional warming have driven a shift toward more diverse phytoplankton assemblages enriched in cyanobacteria, reflecting elevated nutrient inputs and rising temperatures. The observed associations between phytoplankton community changes and sedimentary geochemical proxies suggest that phytoplankton dynamics may not only have responded to environmental change but also contributed to sedimentary biogeochemical cycling, particularly total organic carbon accumulation and calcium‐related processes such as photosynthesis‐induced carbonate precipitation. These findings illustrate long‐term phytoplankton community dynamics and underscore the value of sedDNA for reconstructing ecological trajectories in lake ecosystems.

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

First case report: Severe mass mortality in intensively cultured black scraper (Thamnaconus modestus) caused by nervous necrosis virus infection - Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Zhen Meng; Yingeng Wang; Xiaojun Rong; Meijie Liao; Bin Li; Wenlong Li; Xinzhang Ji; Xiaoyan Cheng; Zheng Zhang (Aquaculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Current warming exceeds medieval warm period in impact on Tibetan Plateau lake ecosystems - Jianan Zheng; Rong Wang; Yu Zhao; Kexin Zhu; Yanjie Zhao; Yuan Li; Ke Zhang; Hao Long; Ji Shen (Quaternary Science Reviews, 2026)

A novel closed-loop path planning algorithm for unmanned surface vessel swarms based on potential field-guided deep Q-learning - Chunhan Zhang; Rong Zhen; Yu Zheng; Yan Zhang; Jialun Liu; Ke Zhang; Chunxu Li (Ocean Engineering, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Distribution of plutonium in a ternary system of water-colloid-bentonite: Implications for radionuclide migration - Yan Liu; Chun Zhang; Yu Wang; Hui Xu; Rong Gong; Jianzheng Zang; Jianbo Liu; Xiang Zhou (Journal of Contaminant Hydrology, 2026)

Corrigendum to “Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide” [Food Res. Int. 230 (2026) 118574] - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying Li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Molecularly integrated dynamic chitosan network with topology-adaptive glucose/ROS responsiveness for coupled drug release and immunoregulation - Yuxiang Li; Sheng Dong; Ran Yu; Runjie Liu; Hengxi Xu; Hainuo Li; Wenbo Ming; Guochao Liao; Rong Zhang; Zhongqiu Liu; Wenxian Wang; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

6H2L, a novel derivative of bifendate, dually suppresses glycolysis and glutaminolysis in hepatocellular carcinoma via inhibiting YAP stability - Beibei Zhang; Kaixuan Sheng; Yue Yan; Xinlei Wang; Xinning Cheng; Rong Liao; Zhiyi Yang; Mengyi Li; Fan Wang; Qi Qi; Yu Wang; Chenglin Li (Chemico-Biological Interactions, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

Unraveling the flame retardant mechanism of protein-rich matrix recovered from anaerobic sludge: The governing role of microstructural characteristics - Bo Zhang; Gaojun Wang; Yinghong Dong; Qian Li; Yu-You Li; Rong Chen (Water Research, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Biochar aging-driven cadmium release in paddy soils: Mechanistic insights into adsorption capacity loss and biochar feedstock-specific risks - Ze-ning Yu; Xiao-qing Zhang; Fei-mei Chen; Rong-liang Qiu; Kuan Zhou; Xin-xian Long (Journal of Environmental Sciences, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

High-efficiency solar-driven photothermal membrane distillation via permeate-side interfacial heating - Qian Yu; Mengfei Xie; Rong Chen; Kuiling Li; Liqiu Zhang; Bo Pan; XueJun Pan; Junhui Zhang; Dan Qu (Desalination, 2026)

Optimizing biochar selection for soil amendment: Unraveling the feedstock-texture interplay for enhanced crop performance - Rong Zhang; Zizhen Ma; Linhua Jiang; Wenjie Gao; Hongping He; Heng Yu; Tao Yu; Bo Yang; Chengtun Qu (Bioresource Technology, 2026)

Unveiling animal death cognition: the role of social systems - Junjie Mu; Xi Yang; Yongbo Li; Yu Huan; Boyi Zhang; James R. Anderson; Rong Hou; Baoguo Li (Science China Life Sciences, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

Protective Effects of Carvacrol Against Vibrio harveyi Infection in Sebastes schlegelii and Its Underlying Mechanisms - Tianwei Wang; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Zhiqi Zhang; Xiaojun Rong; Meijie Liao; Kun Hu; Zheng Zhang (Fishes, 2026)
The inappropriate use of antibiotics in aquaculture has exacerbated antimicrobial resistance in pathogens, thereby reducing the efficiency of aquaculture production. Therefore, it is crucial to develop effective antibiotic alternatives capable of inhibiting pathogenic bacteria. Against this background, the present study investigated the efficacy and underlying mechanism of carvacrol against Vibrio harveyi in the mariculture of the marine fish Sebastes schlegelii, aiming to provide data support for the development of green fishery drugs to replace antibiotics. The results indicated that pre-treatment with carvacrol increased the survival rate of infected S. schlegelii. Meanwhile, post-infection administration of carvacrol alleviated intestinal pathological damage. Carvacrol regulated host immunity by modulating the transcription of the immune-related genes NF-κB/RelA and IL-15. Carvacrol did not significantly alter the activities of SOD, MDA, or CAT, suggesting that the oxidative defense pathway was not primarily involved. Analysis of intestinal Vibrio load confirmed that carvacrol could inhibit the growth and colonization of intestinal Vibrio, thereby maintaining microbial homeostasis. Immunohistochemistry and peripheral blood flow cytometry showed that carvacrol enhanced the adaptive immunity of fish by increasing the proportions of CD4-1+ T cells and CD79a/CD79b+ B cells in tissues and peripheral blood. In conclusion, carvacrol enhances the resistance of S. schlegelii against V. harveyi by inhibiting pathogenic bacteria, improving intestinal morphological structure, reducing pathogenic bacterial load to maintain microbial homeostasis, and enhancing the adaptive immunity of the organism. This study provides a theoretical basis and data support for the substitution of antibiotics and the development of green feed additives in aquaculture.

Successful establishment of denitrification-enhanced anaerobic digestion with nitrate as an exogenous stimulant for effective hydrolysis and methanogenesis of N, N-dimethylformamide-containing wastewater - Zhe Kong; Tao Zhang; Yao Xu; Yong Hu; Chao Rong; Yu-You Li (Water Research, 2026)

Adaptive multi-scale heterogeneous graph-attention network assisted deep reinforcement learning for distributed flexible job-shop scheduling problem - Zi-Qi Zhang; Yu-Han Huang; Yan-Xuan Xu; Bin Qian; Rong Hu (Swarm and Evolutionary Computation, 2026)

Eliminating high-voltage phase transitions and oxygen loss in O3-type sodium layered cathodes via reversible solid-solution and anionic-redox chemistry - Lin-Rong Wu; Yu-Han Zhang; Zhen Wu; Hui Wu; Nian Zhang; Ding Zhang; Xiaochuan Duan; Xian-Ming Zhang (Science Bulletin, 2026)

Efficient Co-hydrothermal conversion of corn straw and pig manure into nitrogen-enriched soluble humic acid fertilizer - Weizhong Huo; Zhaofan Lin; Feng Gao; Jing Yu; Xutong Pang; Rong Ye; Yuchao Shao; Youzhi Miao; Qirong Shen; Ruifu Zhang (Journal of Environmental Management, 2026)

Preparation methods, inhibitory activity, and regulatory mechanisms of angiotensin-converting enzyme inhibitory peptides derived from eggs - Jianbo Wu; Ruihang Luo; Yaqi Rong; Deju Zhang; Jing Zhang; Peng Yu; Yiming Gan (Food Bioscience, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

Magnetic biochar combined with digestate bioaugmentation synergistically accelerates the recovery of a collapsed anaerobic digestion system - Bao-Shan Xing; Yong-Ning Feng; Jia-Yi Liu; Yi Zhang; Guangyin Zhen; Samir Ibrahim Gadow; Rong Chen; Xiaochang C. Wang; Yu-You Li (Chemical Engineering Journal, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Genome-wide identification and promoter activity analysis of fibrillin gene families in different color carrot roots - Yu-Jie Sun; Rong-Rong Zhang; Zi-Han Zhao; Xu Zhang; Xue-Feng Peng; Ya-Hui Wang; Ai-Sheng Xiong (Protoplasma, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Behavioral, Metabolic, and Monoaminergic Responses to Cooked Diets in Southern Catfish (Silurus meridionalis) - Qiushi Yang; Zhimin Zhang; Tingting Xu; Wenhan Li; Huacheng Li; Rong Tang; Yale Deng; Liqin Yu; Xi Zhang; Li Li; Dapeng Li (Fishes, 2026)
Diet form is increasingly recognized as a welfare-relevant factor in intensive aquaculture, yet the effects of feed cooking on fish behavioral and physiological welfare remain poorly characterized. Juvenile southern catfish (Silurus meridionalis; 6.18 ± 0.52 g) were reared for 6 weeks in an indoor recirculating aquaculture system and fed either raw grass carp (Ctenopharyngodon idella) muscle (fish fed raw muscle, FR) or cooked grass carp muscle (fish fed cooked muscle, FC; 15 min ramp to ~100 °C followed by 2–3 min at ~100 °C). Locomotor activity and anxiety-like behavior were assessed using the open-field test and an annular light–dark preference assay, respectively. Flow-through respirometry further revealed a significantly lower standard metabolic rate (SMR) in FC fish than in FR fish, decreasing from 10.30 to 6.83, which represents a 33.7% reduction. Endocrine and biochemical analyses showed that cooking significantly decreased serum total triiodothyronine (T3) by 23.8%, whereas routine serum biochemical indices remained unchanged. In brain tissue, dopamine (DA) was significantly reduced by 7.2% in the FC group, and RT-qPCR analysis of dopamine-related genes further showed a significant downregulation of the rate-limiting synthesis gene th. These results indicate that cooking primarily downshifts the activity-energy axis in southern catfish and is accompanied by coordinated thyroid and dopaminergic changes. To our knowledge, this is the first integrated study to evaluate the behavioral, metabolic, and neuroendocrine effects of cooked feed in S. meridionalis, providing a short-term phenotypic baseline for assessing welfare-relevant feeding scenarios in aquaculture.

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

A CBAM-integrated deep convolutional neural network for weather radar echo correction to overcome terrain occlusion challenge - Hao Wang; Zhihao Liu; Fugui Zhang; Zhi Li; Qiangyu Zeng; Tiantian Yu; Rong Yang (Advances in Space Research, 2026)

The ATG14: multi-layer autophagy control and an emerging therapeutic target in cancer - Wenbo Wang; Chujuan Yu; Fulin Sun; Ruofeng Wang; Weikai Xia; Qinghang Song; Huhu Zhang; Zhenzhen Jia; Min Zhang; Haoran Wang; Zhenxiang Wang; Rong Fu; et al. (Apoptosis, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Single-cell dissection of pleural and systemic immunity uncovers pathogen-specific immune reprogramming in tuberculosis versus lung adenocarcinoma - Sifei Yu; Yueming Liang; Jing Chen; Beiying Zhang; Chuling Zhang; Yuwen Zhao; Rong Yan; Yichu Nie; Xiaofan Mao (Inflammation Research, 2026)

Food sources of the Synaptid Protankyra bidentata and its trophic competition with the sea cucumber Apostichopus japonicus in culture ponds - Jianlong Ge; Teng Lu; Jinjin Wang; Meijie Liao; Xiaojun Rong; Bin Li; Yingeng Wang; Yongxiang Yu; Chunyuan Wang; Zheng Zhang; Zhiqi Zhang (Aquaculture, 2026)

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

A shift in the altitude-dependence of river water isotopes across the Third Pole - Yuanyuan Dang; Tandong Yao; Wusheng Yu; Stephen Lewis; Pengjie Ren; Rong Guo; Zhuanxia Zhang; Jingyi Zhang (Science Bulletin, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Significant suppression of sulfur–containing organic aerosols by emission controls during the Hangzhou Asian Games - Jintian Zhang; Lei Liu; Jianxiong Rong; Lin Du; Zechen Yu; Shanshan Tang (Journal of Environmental Sciences, 2026)

Microwave treatment enhances brown rice edible quality: Deciphering moisture content-driven modulation of microstructure, moisture distribution and starch properties - Yang Yu; Jiayu Zhang; Dan Ouyang; Rong He; Kai Huang; Shangyuan Sang; Yanan Liu; Jiali Xing; Ying Wan; Xiaohu Luo (Journal of Cereal Science, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Cold adaptation strategies of anammox bacteria and the bottleneck of nitrogen removal performance in autotrophic nitrogen removal process treating digested swine wastewater - Ya-hui Wang; Fang-yu Huang; Long-xing Jiang; Rong You; Yun-hong Zhang; Liang-wei Deng; Wen-guo Wang; Lan Wang (Chemical Engineering Journal, 2026)

Reduced graphene oxide enhances emerging contaminants removal in anaerobic wastewater treatment: Synergistic role of adsorption and microbial metabolism - Lianxu Wang; Zixin Zhang; Youfei Zhou; Zhen Lei; Yuan Yang; Yu-You Li; Rong Chen (Bioresource Technology, 2026)

Microbial metabolic traits regulate the difference in microbial necromass contribution to SOC between rhizosphere and bulk soil - Yu Zhou; Jing Yu; Donghui Liu; Rong Liu; Yunchu Zhang; Juan Xiao (Plant and Soil, 2026)

Tropical instability waves and their relationships with large-scale oceanic thermal conditions, revealed in ROMS-based hybrid coupled model of the tropical Pacific - Yinnan Li; Yang Yu; Chuan Gao; Hongna Wang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Mediating role of metabolic dysfunction-associated fatty liver disease in the association between individual-level noise exposure and liver enzymes in Chinese automotive manufacturing workers - Sijia Ou; Jiaheng Yu; Zhaoqian Chen; Yanmei Ruan; Xing Rong; Zejin Ou; Yuxia Zhang; Haijuan Huang; Jiaxin Cui; Zhi Wang (International Archives of Occupational and Environmental Health, 2026)

Automatic Detection of Disaster-Causing Organisms near the Waters of Nuclear Power Plant Based on LiveScope Scanning Sonar Images - Gangyi Yu; Shuo Wang; Wei Liu; Yongjian Xia; Yuchen Guo; Xiaolu Chen; Xueping Wei; Ao Chen; Zehua Lv; Chao Lu; Junbo Zhang; Rong Wan (Journal of Marine Science and Engineering, 2026)
Nuclear power serves as an efficient, clean, and low-carbon energy source that constitutes a significant component of the energy portfolio in numerous countries. Most nuclear power plants are predominantly situated in coastal regions, utilizing seawater as the ultimate heat sink for their cooling systems. Real-time monitoring of marine organism dynamics near water intakes is essential to mitigate the risk of unit shutdowns triggered by outbreaks of disaster-causing organisms (DCOs). This study employed LiveScope scanning sonar videos captured near the Ningde Nuclear Power Plant to develop a dataset for detecting the light spot area of the DCOs. We proposed a directionally optimized model, Bio-YOLO v7, which significantly enhances the detection of small targets in sonar images. The Bio-YOLO v7 model achieved precision, recall, and average precision rates of 85.29%, 83.28%, and 81.49%, respectively, demonstrating superior performance in identifying DCOs near the intakes of nuclear power plant. The light spot size of the DCOs exhibited significant periodic variations, serving as a crucial indicator for forecasting outbreak events.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Synergistic effects of climate forcings from three oceans on the reserve of “Atmospheric water tower” over the Tibetan Plateau - Pengjie Ren; Wusheng Yu; Stephen Lewis; Yaoming Ma; Yuanyuan Dang; Lei Zhong; Zhuanxia Zhang; Yong Liu; Lun Luo; Zhaowei Jing; Jingyi Zhang; Rong Guo; et al. (Journal of Hydrology, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Sustained polyhydroxyalkanoate recovery from fermentative food wastewater in a one-stage mixed microbial culture system under aerobic dynamic discharge strategy: Effects of organic loading rate and substrate composition - Xiang Zhang; Ji Zhang; Gaojun Wang; Kexin Wang; Yanfang Ma; Qian Li; Yu-You Li; Rong Chen (Journal of Cleaner Production, 2026)

LSTM-CNN-CBAM-based prediction of NOx emissions with zonal control strategies for flexible peak-load NOx reduction in CFB coal-fired units - Jing Wang; Xinwen Liao; Yu Che; Pengcheng Wang; Yuanyuan Zhang; Fei Wang; Frédéric Marias; Haojie Rong (Journal of Cleaner Production, 2026)

Klebsiella aerogenes HC10 protecting hydrogel for Sb(III) removal: Performance and mechanism - Chaolan Zhang; Kai Zhong; Dingtian Lu; Junyu Xiang; Yubo Sun; Sirong Yu; Liwen yuan; Huan Deng; Minhua Gu; Qun Rong (Journal of Environmental Chemical Engineering, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Constructing a core-shell heterojunction with photo-activated antifouling shield via interface engineering for uranium extraction from water - Yue Ma; Yilei Zhang; Huazhen Rong; Jinjiao Pan; Chuan Gan; Zhuoming Yang; Yu Guo; Yihui Yuan; Ning Wang (Desalination, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Self-assembly of bayberry-like porous BiVO4 nanospheres for self-powered marine underwater optical communication - Ping Wang; Shuai Ren; Kun Fu; Yizhou Lv; Yayue Wang; Ping Rong; Weipeng Chen; Jianhua Zhang; Xifei Li; Qi Yu (Chemical Engineering Journal, 2026)

Beyond decline: spatial heterogeneity of soil organic matter as an emerging signal of cropland degradation in Northeast China - Chong Luo; Depiao Kong; Yu Zhang; Rong Bai; Huanjun Liu (CATENA, 2026)

Robust copper/mesoporous silica catalyst for efficient furfural hydrogenation to furfuryl alcohol - Xin-Yu Xiao; Jie Zhang; Rong Wang; Qi Wang; Hai-Song Li; Jing-He Yang (Biomass and Bioenergy, 2026)

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Effects of mineral inputs on organic phosphorus (Adenosine 5′-monophosphate) sorption and implications for its biogeochemical behavior on marine sediments - Yu Meng; Meng Lv; Xiao-Tong Zhang; Xiao-Yan Cao; Rong Chen; Gui-Peng Yang (Marine Chemistry, 2026)

Efficient low-temperature NO reduction via constructing Cu+ −O−Co3+ sites to enhance lattice oxygen release and CO adsorption - He Wang; Ye Zhu; Wei Wang; Xiaoqing Dang; Yufei Zhang; Dandan Zhu; Rong Li; Dongjie Yan; Qian Ma; Jiaxin Qu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Metallogenic constraints of sandstone-hosted uranium deposits in arid red beds: A case study from the northwestern Santanghu Basin - Hui Rong; Jun Zhou; Yu Zhou; Yuchen Zhang; Min Liu; Kaiyu Chang (Journal of Geochemical Exploration, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Comprehensive review of constructed wetlands implemented with advanced biotechnologies for carbon-neutral treatment of urban wastewater: Enhanced removal of nitrogen and reduction of greenhouse gas emissions - Feifei Jiao; Xuyihui Chen; Tao Zhang; Chengde Sun; Bin Qi; Shichuang Xu; Xuefei Zhou; Yalei Zhang; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; et al. (Bioresource Technology, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

Taxonomy and phylogeny of Erysiphe species on Liquidambar formosana (Hamamelidaceae) - Jing Feng; Shuang-Bao Wang; Shu-Yan Liu; Michael Bradshaw; Uwe Braun; Shou-Rong Yu; Guan-Xiu Guan; Dan-Ni Jin; Zhao-Yang Zhang; Han-Xing Gao (New Zealand Journal of Botany, 2025)

Side-stream anaerobic membrane bioreactor system for energy-positive sewage treatment - Chao Rong; Weifu Yan; Ying Song; Chunxiao Wang; Zhiguo Yuan; Yu-You Li; Tong Zhang (Water Research, 2025)

Significant generational effects of tetracyclines upon the promoting plasmid-mediated conjugative transfer between typical wastewater bacteria and its mechanisms - Lingling Rong; Baoyin Zhang; Hongmu Qiu; Hailin Zhang; Jiayin Yu; Qing Yuan; Ligui Wu; Hong Chen; Yuanmin Mo; Xiaoming Zou; Xubiao Luo (Water Research, 2025)

Neonicotinoids and human health: Environmental fate, toxicity mechanisms, and future directions - Kangming Ji; Yu Rong; Zihang Zhang; Yunjie Chen; Ruixin Hu; Yuchen Chu; Yuyi Tang; Lijun Qian; Chuang Yang (Pesticide Biochemistry and Physiology, 2025)

One new aryltetralin lignan and other components from Blachia pentzii - Yan-Yan Zhang; Feng-Cheng Zhang; Yue Zhang; Hong-Yan Yu; Hai-Rong Xu; Xiao-Yun Dong; Chang-Shui Yang (Phytochemistry Letters, 2025)

Reversing the paradigm: Oxygen-dependent switch of nTiO₂ from promoting to suppressing ARG conjugation - Jie Yu; Xin Wang; Ya-Xin Hu; Feng-Ting Cao; Qiu-Rong Zhang; Xiang-Tong Zhou; Xiang Xiao (Journal of Hazardous Materials, 2025)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Construction of antibacterial-enhanced 2D ZnO@ZIF-8 nanocomposites based on synergistic antimicrobial mechanisms and application in maize long-term storage - Song-Yue Xu; Chao-Shuai Mei; Ke-Yu Zhou; Feng Xiao; Min Zhang; Qiong Wu; Yu-Rong Zhang; Dong-Dong Zhang (Food Chemistry, 2025)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Zearalenone accelerates aging and mitochondrial dysfunction: Evidence from network toxicology and zebrafish models - Rong Li; Ziyuan Zhang; Yu Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Wood-derived self-standing carbon electrodes for electrocatalysis: design, performance, and prospects - Liu-Liu Shen; Xinkun Li; Peiran Wu; Jiansong Wang; Hui Yu; Yipu Xu; Yuhang Wang; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2025)

Synergistic interfacial engineering and ion transport kinetics in high-safety PEO-based polymer electrolytes - Hong-Yu Wang; Kun-Rong Lu; Yue-Xi Han; Fa-Nian Shi; Peng-Fei Wang; Yu-Hang Zhang (Chemical Engineering Journal, 2025)

An injectable and programmable hydrogen delivery system for modulation tendon tissue in tendon-bone interface microenvironment - Tao Yuan; Fei Jin; Lili Qian; Xiaojiang Yang; Xin Yu; Zhongyang Lv; Ziying Sun; Shiwen Shen; Hong Qian; Jia Meng; Hui Jiang; Wenshuang Sun; et al. (Chemical Engineering Journal, 2025)

Activated carbon facilitates Saccharomyces cerevisiae colonization in an electron-donor self-sustaining chain elongation fermentation system - Weizhong Huo; Zhaofan Lin; Rong Ye; Jing Yu; Ruifu Zhang; Qirong Shen (Bioresource Technology, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Specnuezhenide mitigates tunicamycin-induced liver injury in mice via ER stress modulation and metabolic reprogramming - Tianle Zhang; Dan Bi; Jiahui Li; Xin Jin; Huijuan Wu; Changyuan Yang; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Molecular Biology Reports, 2025)

Correction: Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Competent expression of effective and long-acting human α-Gal A-Fc fusion protein in the milk of transgenic mice - Mengke Yuan; Lan Yang; Chunyang Li; Zhiqiang Wu; Zhipeng Liu; Tianfei Du; Xinzong Rong; Cong Cong; Yongxia Zhang; Xiaoping Yu; Yali Gao; Zhengli Chen; et al. (Transgenic Research, 2025)

The high-affinity K+ transporter IbHAK5 enhances potassium ion absorption and improves root morphology in sweetpotato (Ipomoea batatas) - Rong Jin; Peng Zhao; Mengxiao Yan; Ming Liu; Weijuan Fan; Qiangqiang Zhang; Xiaoya Zhu; Jing Wang; Yongchao Yu; Jun Yang; Hongxia Wang; Zhonghou Tang (Transgenic Research, 2025)

Structural variation in the promoter region of DcSOC1d influences flowering behavior in carrot - Kai Zhang; Rong-Hua Wu; Yu-Min Zhang; Ai-Sheng Xiong; Zhi-Sheng Xu (Journal of Plant Physiology, 2025)

Synergistic effects of biochar and E. coli on reducing cadmium bioavailability and improving soil fertility through enhanced bacterial-fungal interactions - Quan Chen; Rongrong Lin; Wan-Rong Zhang; Yafeng Wang; Yanqing Xiong; Pengfei Wang; Yu Huang; Min Wu; Peng Yi; Bo Pan (Journal of Hazardous Materials, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

The dynamic succession of the core microbial communities in pasteurized milk during refrigeration based on metagenomics - Chunyan Hu; Rong Guo; Jiao Zhuang; Yan Gao; Xia Zhang; Yu Meng; Zhen Liu; Yongxia Bian; Liqing Wu; Shuai Guo; Ning Ju (International Dairy Journal, 2025)

Fermentation-derived dihydroferulic acid from Cordyceps militaris binds AKT1 to protect intestinal epithelial health - Rong Huang; Jixing Gao; Zelin Wang; Jie Cai; Zhenjun Zhu; Qingping Wu; Juan Wang; Fen Zhang; Yu Ding (Food Bioscience, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

Compartment engineering in yeast: a path to increased biochemical production - Yuyang Wang; Liyan Cao; Lanxin Rong; Chen Ding; Chang Liu; Qingqing Ye; Qingeng Huang; Cui-ying Zhang; Ning Xu; Jiwei Mao; Jee Loon Foo; Aiqun Yu (Chemical Engineering Journal, 2025)

Establishment of regeneration and CRISPR/Cas9-mediated genetic transformation systems in Impatiens walleriana - Huang Deng; Yulu Wu; Shanman Li; Baiyang He; Yuteng Xue; Shunming Zhang; Xue Hu; Yu Zhou; Jiwei Wang; Yuhang Wang; Songtao He; Yuhong Rong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Gut microbiota-metabolite dynamics in Sebastes schlegelii following Vibrio harveyi infection - Yindong Gu; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Zhiqi Zhang; Xiaojun Rong; Meijie Liao; Lei Qin; Bin Li; Zheng Zhang (Aquaculture International, 2025)

Microenvironment-regulated UiO-67-based metal-organic frameworks for efficient removal of perfluorohexanoic acid from water - Xiaoxia Zhang; Xinyuan Zeng; Meng Rong; Mingchuan Yu; Hongtao Yu; Junfeng Niu (Journal of Hazardous Materials, 2025)

Anthraquinone-2,6-disulfonate (AQDS) modified bio-cathode stimulated chain elongation process in electro-fermentation systems for caproate production - Weizhong Huo; Rong Ye; Zelin Zheng; Jing Yu; Zhaofan Lin; Ruifu Zhang; Qirong Shen (Journal of Environmental Chemical Engineering, 2025)

Sustainable nutrients removal from low-strength wastewater: A comprehensive review of biofiltration for resource recovery and carbon neutrality - Chengde Sun; Guangyi Ma; Bin Qi; Kun Wu; Tao Zhang; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; Zhe Kong (Journal of Environmental Chemical Engineering, 2025)

CTAB-Assisted, controlled preparation of a CeZrOx/CuSAPO-34 catalyst and its performance for the synergistic removal of NOx and toluene from flue gas - Qian Zhou; Xuehui Jia; Rong Liu; Fangfei Liu; Han Zhang; Dan Hou; Lu Wang; Yunkuo Luo; Bichun Huang; Hong Huang; Xia Gong; Chenglong Yu (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

A hydraulic conductivity model for unsaturated bentonite-based materials incorporating surface enhanced vapour diffusion - Zhang Rong LIU; Yu Jun CUI; Wei Min YE; Yong Gui CHEN; Qiong WANG (Computers and Geotechnics, 2025)

Analysis of starch structure, functional properties, and the underlying molecular mechanism in SeaRice86 (SR86) - Yongxiang Huang; Xiao Yang; Yilan Cui; Mangu Hu; Yunliang Rong; Yu Ling; Rongchao Yang; Yueqin Zhang (Carbohydrate Polymers, 2025)

Research on quantitative monitoring of new meteorological-agricultural compound drought characteristics - Yang Yu; Lei Zhou; Wenliang Wang; Rong Tian; Jingxin Zhang; Senmiao Hu; Qingzhu Zhang; Yalan Li (Theoretical and Applied Climatology, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Longitudinal analysis of metabolic liver disease induced by high-starch diets in largemouth bass (Micropterus salmoides) - Xixuan Huang; Xuemei Ouyang; Li Wang; Kun Xue; Haodong Yu; Chenlei Liao; Feifei Chen; Keming Rong; Xuezhen Zhang (Aquaculture International, 2025)

Hydroxyl Radical‐Driven Oxidation as a Key Pathway for Greenhouse Gas Production During Soil Drying–Rewetting - Xing Guo; Yongxing Lu; Jungang Yang; Fan Du; Yakov Kuzyakov; Yuanhe Yang; Shen Yu; Shuping Qin; Qinglong Fu; Xiaoying Rong; Benfeng Yin; Kai Shi; et al. (Global Change Biology, 2025)
The drying‐rewetting of soil can increase the release of greenhouse gases over a short time period and is one of the key pathways for greenhouse gas emissions in many terrestrial ecosystems, particularly in drylands. The mechanisms underlying this pulse of greenhouse gas emissions remain nearly unknown. Here, we conducted simulated soil rewetting experiments using typical cover of dryland soils (bareland, cyanobacteria/lichen‐covered soil, and moss‐covered soil). The 13 C, 15 N, and 18 O labeling techniques allowed to explore the intrinsic mechanisms of rapid carbon (C) and nitrogen (N) release from the soils following rewetting. We found that the hydroxyl radical (˙OH) was produced after soil rewetting via the rapid activation of microorganisms. The carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) production strongly decreased after ˙OH removal, whereas the methane (CH 4 ) production was not affected. The synergistic action between ˙OH oxidation and microbial enzymatic reactions increased CO 2 production. The ˙OH also stimulated the oxidation of NH 4 + to NO 3 − and dominated the N 2 O production. Our results confirm the role of ˙OH in the production of greenhouse gases and indicate that microbially mediated ˙OH oxidation mechanisms are an overlooked key pathway for the emission of greenhouse gases during the soil rewetting. In the context of climate change, the extreme weather‐induced drying‐rewetting cycles in soils are becoming more frequent, making greenhouse gas emissions via the ˙OH oxidation pathway increasingly important.

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Radionuclide tracers reveal seasonal dynamics of particle-associated pollutants in the Jiulong Jiang Estuary, a subtropical tidal estuary - Dekun Huang; Jieran Zhang; Rong He; Fule Zhang; Qiangqiang Zhong; Li Bin; Tao Yu (Marine Pollution Bulletin, 2025)

Accurate and simple determination of sediment redox capacity by a modified chemical probe method: Implications to contaminant remediation - Yuxi Lu; Rong Chen; Weijun Zhao; Peng Zhang; Shukui Zhu; Chenglong Yu; Songhu Yuan (Water Research, 2025)

Biogenic Cu2-xSe nanoparticles with vacancy engineering quickly upcycle cobalt from wastewater for photothermal antibacterial and desalination - Xue-Meng Wang; Zhi-Xuan Zhang; Yun-Jie Wang; Hao-Yu Li; Wen-Wei Li; Rong Chen (Water Research, 2025)

Antimicrobial-enhanced nanoparticles based on self-assembly effects: principles, properties and applications in food - Song-Yue Xu; Jin Zhang; Ke-Yu Zhou; Min Zhang; Qiong Wu; Yu-Rong Zhang; Dong-Dong Zhang (Trends in Food Science & Technology, 2025)

Formation of the giant Jinduicheng porphyry Mo deposit in East Qinling, Central China: Evidence from geochemical and isotopic compositions of magmatic accessory minerals - Kai Xing; Qihai Shu; David Lentz; Rong Xu; Fangfang Zhang; Jinyu Liu; Fan Yu; Xudong Niu; Qingfei Wang; Jun Deng (Lithos, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

The evolutionary history of the Methyltransf_FA domain and its role in JH signal in silkworm, Bombyx mori - Chunyang Wang; Yang Yu; Qi Shen; Rong Xiong; Meiwei Guo; Jiamei Zhao; Dongsheng Yan; Rongcheng Zhang; Ping Chen (Insect Biochemistry and Molecular Biology, 2025)

Radionuclides and heavy metals in surface sediments of the Bering and Chukchi Seas: distribution, source identification, and risk assessment - Jing Lin; Qiangqiang Zhong; Rong He; Fule Zhang; Hao Wang; Liang Wang; Dekun Huang; Tao Yu (Continental Shelf Research, 2025)

Donor-receptor coordination mediated multiple antigens capture and transport for augmented cancer immunotherapy - Huan Liang; Qingqing Lu; Runyu Hu; Yixiao Zhang; Xing Rong; Guocan Yu; Jie Yang (Chemical Engineering Journal, 2025)

Biomembrane delivers neurotrophic factor for spinal cord injury recovery through microneedle patch - Bowen Zheng; Mingpai Ge; Jing Zhang; Tao Zhu; Yu Yi; Hongtao Rong (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

A synergistic water-saving strategy combining stage-specific irrigation and application of exogenous thiamine enhances drought resistance of Xinjiang cotton - Fuxiang Zhao; Linjie Xia; Simin Sun; Hang Li; Yuxuan Rong; Yuxin Wang; Xuwen Wang; Xianhui Kong; Longfu Zhu; Xianlong Zhang; Yu Yu; Xiyan Yang (Plant and Soil, 2025)

Distinct mechanisms of marine heatwave formation in offshore waters of China - Zhibo Chen; Ying Wang; Jiaqi Wang; Rong-Hua Zhang; Yifan Jiang; Yu Qi; Xinchi Yu (Journal of Oceanology and Limnology, 2025)

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Low Nitrogen with Split Application Strategy Enhances Antioxidative Defense, Photosynthesis, and Enzymatic Activities to Waxy Maize Under Heat Stress - Song Xu-dong; Ahmad Irshad; Zhang Hui-min; Zhang Zhen-liang; Zhou Guang-fei; Chen Guo-qing; Mao Yu-xiang; Lu Hu-hua; Hao De-rong (Journal of Plant Growth Regulation, 2025)

Polymeric immunoglobulin receptor (pIgR) in cancer progression: a critical role and potential therapeutic target - Shaoju Qian; Yeqing He; Ruixue Li; Panpan Sun; Xingyi Zhang; Lin Pan; Zhishan Xu; Zhiwei Feng; Rong Lian; Lili Yu (Apoptosis, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Technological advances and sustainable strategies for electrolytic manganese wastewater treatment: A critical review - Chenyang Zhang; Ronghao Du; Rong Wang; Wei Sun; Yueping Luo; Zhiyuan Yu (Process Safety and Environmental Protection, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Enhanced ethanol-driven carboxylate chain elongation by MOF-808 from waste activated sludge: Process and mechanism - Weizhong Huo; Jing Yu; Rong Ye; Zhaofan Lin; Ruifu Zhang; Qirong Shen (Journal of Environmental Management, 2025)

Characteristics of nitrogen and phosphorus migration at sediment-water interface in seasonal frozen lakes and the mechanism of microbial driven cycling: a case study of Lake Daihai - Rong Wu; Xiaohong Shi; Xueer Kang; Sheng Zhang; Shengnan Zhao; Yu Liu; Biao Sun; Junping Lu; Haifeng Yu; Shihuan Wang; Xueru Pan; Kaiqi Shen; et al. (Journal of Contaminant Hydrology, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Sustainable production of phloretin using multi-dimensionally adjustable acidic deep eutectic solvents as multifunctional solvents for green and efficient valorization of Malus plant pruning waste - Rong Wu; Lu Zhang; Kehong Liang; Feng Zhu; Longxin Lai; Jun Cao; Pengfei Yu; Fuliang Cao; Erzheng Su (Food Bioscience, 2025)

Aging influence and long-term stable mechanism of biofuel ash immobilizing cadmium in alkaline soil combining artificial aging simulation - Le Song; Wengeng Cao; Yu Ren; Rong Zhang; Zhaoji Zhang; Jiazhong Qian (Environmental Research, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Enhanced ecological risks of pollutant-adsorbed engineered environmental particles to soil microorganisms - Quan Chen; Yue Zhang; Wan-Rong Zhang; Yu Huang; Min Wu; Hong-Zhe Li; Yi-Yue Zhang; Yi-Fei Wang; Dong Zhu; Philippe Frangois-Xavier Corvini; Bo Pan (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Soil invertebrate diversity supports ecosystem multifunctionality along elevation gradients - Xiao-Min Zeng; Manuel Delgado-Baquerizo; Shuhai Wen; Jiao Feng; Wen Zhang; Qianggong Zhang; Yu-Rong Liu (Plant and Soil, 2025)

A hybrid coupled model for the tropical Pacific constructed by integrating ROMS with a statistical atmospheric model - Rong-Hua Zhang; Wenzhe Zhang; Yang Yu; Yinnan Li; Feng Tian; Chuan Gao; Hongna Wang (Journal of Oceanology and Limnology, 2025)

Semi-Supervised Maritime Object Detection: A Data-Centric Perspective - Meng Wu; Weilong Zhang; Rong Min; Lei Zhang; Yueting Xu; Yuheng Qin; Jing Yu (Journal of Marine Science and Engineering, 2025)
Semi-supervised object detection (SSOD) has emerged as a promising technique to boost the performance of the detectors, utilizing both labeled and unlabeled data. However, in marine environments, SSOD faces formidable challenges posed by complex conditions like shore-based landscapes, varying ship scales, and diverse weather, which complicate data acquisition and thus the generation of accurate pseudo-labels. To tackle these issues, we propose two novel strategies, depth-aware pseudo-label filtering (DAPF) and dynamic region mixup (DRMix) augmentation, from a data-centric perspective. Specifically, the DAPF strategy incorporates depth information as a prior to refine pseudo-labels by filtering out unreliable ones, thereby improving the quality of pseudo-label–data pairs used for training. Meanwhile, DRMix augmentation dynamically mixes images at the regional level, generating diverse and representative data suitable for maritime object detection tasks. Extensive experiments on maritime datasets validate the effectiveness of our approach, achieving mAP improvements of 2.2% on the SeaShips dataset and 0.9% on the Singapore Maritime dataset compared to other state-of-the-art (SOTA) methods. Our code will be made publicly available.

Synergistic estimation of mangrove canopy height across coastal China: Integrating SDGSAT-1 multispectral data with Sentinel-1/2 time-series imagery - Mingming Jia; Rong Zhang; Chuanpeng Zhao; Yaming Zhou; Chunying Ren; Dehua Mao; Huiying Li; Genyun Sun; Hongsheng Zhang; Wensen Yu; Zongming Wang; Yeqiao Wang (Remote Sensing of Environment, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Divergent effects of biomass-derived carbon dots application and sweetpotato planting on accumulations of soil microbial necromass carbon in Vertisol - Jing Wang; Meng Zhu; Xiaoya Zhu; Qiangqiang Zhang; Yongchao Yu; Peng Zhao; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhanced microbial degradation of hexabromocyclododecane in riparian sediments through regulating flooding regimes - Juan Chen; Rong Wang; Chao Wang; Peifang Wang; Han Gao; Yu Hu; Qihao Nie; Shunqing Zhang (Journal of Hazardous Materials, 2025)

Nanomedicine constructed with plant-derived aromatic aldehydes treats low back pain by reversing the progression of lumbar facet joint osteoarthritis - Ming Yang; Hui Lv; Zhenzhen Tang; Jiangling Zhou; Qiandong Yang; Juan Cai; Yingtao Gui; Bo Yu; Rong Huang; Jing Yang; Ying Bao; Dinglin Zhang; et al. (Chemical Engineering Journal, 2025)

Green recycling of end-of-life photovoltaic modules via deep-eutectic solvents – Part B - Yuelong Yu; Jianghao Shi; Xinjie Bai; Zhansheng Zhang; Fengshuo Xi; Shaoyuan Li; Jijun Lu; Wenhui Ma; Rong Deng (Chemical Engineering Journal, 2025)

Identification of the chemical composition of blue honeyberry leaves (Lonicera caerulea L. var. edulis) and their anti-inflammatory activity - Zhenji Rong; Chunping Yu; Xin Wang; Ruyue Wang; Yang Gao; Hailong Zhang (Medicinal Chemistry Research, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

A new sesquiterpene from endophytic fungus Colletotrichum sp. B-89 - Ke-tao Zhang; Bing Zhang; Zhi-pu Huang; Yu-xiao Xu; Xiao-rong Xu; Si-heng Li; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2025)

Potential role of Mc3r and Mc4r in ovarian metabolism and development in female red crucian carp (Carassius auratus red var.) - Faxian Yu; Lu Huang; Xinxin Yu; Shuxin Zhang; Shengnan Li; Rong Zhou; Wenjing Tao; Lanying Yang; Min Tao; Qizhi Liu; Shaojun Liu (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Self-powered and self-sensing water meter using contact-separation triboelectric nanogenerator with harvesting local head loss - Da-Qi Cao; Xiao-Dan Liu; Rong-Kun Fang; Guri Yihuo; Yun-Feng Wu; Zhan-Gao Huang; Wen-Yu Zhang; Xiangyu Chen; Xiao-Di Hao (Journal of Water Process Engineering, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Surface ammonification regulates oxygen vacancies and acidic sites in δ-MnO2 to enhance low-temperature selective catalytic oxidation activity of ammonia - Yu Zhou; Huiyu Zhang; Jingling Lu; Wang Ran; Shaopeng Rong (Journal of Environmental Management, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Synergistic enhancement of flame retardancy, mechanical properties, dimensional stability, and mold resistance in bamboo via silica mineralization and hydrophobic treatment - Lu He; Gege Bao; Xi Yu; Xiaofeng Zhang; Xiaobei Jin; Zixuan Yu; Rong Zhang; Daochun Qin (Chemical Engineering Journal, 2025)

DcNCED2 promotes ABA synthesis via carotenoid degradation and enhances drought resistance in carrot - Rong-Rong Zhang; Ya-Hui Wang; Xue-Feng Peng; Yu-Jie Sun; Nan Zhang; Ai-Sheng Xiong (Plant Cell Reports, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Vanillic acid ameliorates collagen-induced arthritis by suppressing the inflammation response via inhibition of the MAPK and NF-κB signaling pathways - Yu Zhou; Pengfei Li; Zhongwen Zhi; Rong Chen; Chenghai Li; Chunbing Zhang (Inflammopharmacology, 2025)

Overexpressing IbHAK5 increases drought stress tolerance in transgenic sweetpotato - Rong Jin; Peng Zhao; Qiangqiang Zhang; Ming Liu; Xiaoya Zhu; Jing Wang; Yongchao Yu; Zhonghou Tang (Plant Biotechnology Reports, 2025)

Dietary mixed-oxysterols and 27-Hydroxycholesterol induce cognitive impairment by regulating gut microbiota and miR-144-3p in vivo - Tao Wang; Mengwei Ju; Xiaona Zhang; Wenjing Feng; Lijing Wang; Ling Hao; Huiyan Yu; Rong Xiao (GeroScience, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

A novel pretreatment process for vanadium extraction: Purification and recovery of negative component calcium in vanadium-bearing steel slag - Guohua Ye; Yun Zhang; Yu Xie; Xinyue Xiang; Yiyang Rong; Changxu Song (Process Safety and Environmental Protection, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Regulation of ethanol production from anaerobic fermentation of food waste using aromatic alcohol-based quorum-sensing molecules - Rong Ma; Zhuoshen Huang; Yi Jiang; Anqi Zhao; Guangwei Yu; Changquan Lin; Langping Zhu; Xiaozhi Zhang; Xiaotian Li; Chunming Wang (Journal of Environmental Management, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Trade-offs between agronomic and environmental benefits: A comparison of inhibitors with controlled release fertilizers in global maize systems - Minyu Wang; Ping He; Daijia Fan; Rong Jiang; Guoyuan Zou; Daping Song; Libo Zhang; Yu Zhang; Wentian He (Field Crops Research, 2025)

Nanometabolomics elucidated biological response of 3D printed vascular stents: Towards metabolic reprogramming of metabolome and lipidome - Yu Zeng; Yumeng Liu; Tong Sun; Ge Liang; Luolan Gui; Wen Zheng; Lu Zhang; Yuanping Gao; Yunfei Dang; Rong Fan; Yang Lu; Dingkun Zhang; et al. (Chemical Engineering Journal, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Transcutaneous Auricular Vagus Stimulation Attenuates LPS-Induced Depression-Like Behavior by Regulating Central α7nAChR/JAK2 Signaling - Junying Wang; Yu Wang; Yu Chen; Jinling Zhang; Yue Zhang; Shaoyuan Li; Haohan Zhu; Xingke Song; Liwei Hou; Lei Wang; Yifei Wang; Zixuan Zhang; et al. (Molecular Neurobiology, 2025)

Foliar-Applied Carbon Dots Confer Enhanced Low Phosphorus Tolerance in Sweetpotato Seedling - Xiaoya Zhu; Jing Wang; Peng Zhao; Qiangqiang Zhang; Yongchao Yu; Ming Liu; Rong Jin; Zhonghou Tang (Journal of Soil Science and Plant Nutrition, 2025)

Evaluations of two ion temperature models in IRI-2020 based on the observations from ICON and COSMIC-2 IVM - Tingwei Han; Huijun Le; Shun-Rong Zhang; Vladimir Truhlik; Natalie Reeves; Angkita Hazarika; Yujin Cho; Mei-Yu Chen; Libo Liu; Yiding Chen; Ruilong Zhang (Advances in Space Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Distributions of DMS and DMSP and the influences of planktonic community assemblages in the Bohai Sea and Yellow Sea - Juan Yu; Yu Jiang; Rong Chen; Jing-Guang Lai; Hou-Jin Zhou; Yong-Qiao Chen; Qi Zhang; Gui-Peng Yang (Marine Environmental Research, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Integrating larval zebrafish model and network pharmacology for screening and identification of edible herbs with therapeutic potential for MAFLD: A promising drug Smilax glabra Roxb. - Yinjuan Xiong; Xixuan Huang; Yuxin Li; Yukang Nie; Haodong Yu; Yaqi Shi; Jiajie Xue; Zhehui Ji; Keming Rong; Xuezhen Zhang (Food Chemistry, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Multi-omics analysis and longitudinal study of reprogramming by dietary creatine to endogenous metabolism in largemouth bass (Micropterus salmoides) - Haodong Yu; Yukang Nie; Xinping Ran; Shaoyun Li; Keming Rong; Xuezhen Zhang (Fish Physiology and Biochemistry, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Identification of Boveria labialis parasitism in the respiratory tree of the Cultured Sea cucumber, Apostichopus japonicus - Wenyue Hao; Xiaojun Rong; Meijie Liao; Bin Li; Yingeng Wang; Jianlong Ge; Jinjin Wang; Zheng Zhang; Yongxiang Yu (Aquaculture, 2025)

Study on the mechanism of brain injury caused by acute diquat poisoning based on metabolomics - Chaocheng Wang; Hui Hu; Junzhao Liu; Xia Rong; Jing Zhang; Yu Du (Toxicology and Applied Pharmacology, 2025)

Experimental study on hydraulic performance and cavitation characteristics of a R134a refrigerant self-lubricating centrifugal pump - Ze Zhang; Song Yang; Beile Zhang; Xufeng Fang; Rong Xue; Shuangtao Chen; Yu Hou (International Journal of Refrigeration, 2025)

Inhibition of fungal mycelial growth and mycotoxin production using ZnO@mSiO2 nanocomposite during maize storage - Song-Yue Xu; Zi-Yi Wang; Qiong Wu; Feng-Wei Hu; Jin-Feng Zhao; Yu-Rong Zhang; Dong-Dong Zhang (Food Bioscience, 2025)

Fast detection of NO2 by In2O3@ZnO nanofibers synthesized by coaxial electrospinning: Real-time monitoring application of smart mask - Xingyu Kang; Haibo Yu; Xiao Ma; Eryang Shang; Hong Chen; Huizhang Zhao; Jiawei Zhang; Rong Tan; Dong Wang; Hairui Fang (Chemical Engineering Journal, 2025)

Ternary Ni:Fe- activated inert Cu-based electrocatalyst as efficient bifunctional electrocatalysts for water splitting - Shi-Yu Lu; Chunjie Wu; Tingting Hu; Ling Wang; Wenzhao Dou; Jun Zhang; Rong Wang; Yin Liu; Qian Yang; Zhigang Zou; Meng Jin (Chemical Engineering Journal, 2025)

High/Low-Index Faceted PdNi Alloy Nanocrystals as Highly Active and Stable Electrocatalyst for Oxygen Reduction - Jun Zhang; Xinlan Xu; Lanyu Luo; Tiantian Peng; Boyu Liu; Lingying Jiang; Meng Jin; Rong Wang; Huan Yi; Weimin Wu; Shi-Yu Lu (Chemical Engineering Journal, 2025)

Sunflower-inspired smart evaporator with omnidirectional solar tracking for highly enhanced energy-capturing and sustainable freshwater harvesting - Yuchun Shen; Rong Zhang; Guodong Hou; Yu Chen; Peng Yang; Xiaoshi Qian; Shaochun Tang (Chemical Engineering Journal, 2025)

Box-shaped necklace-like Fe3O4/MoS2-CNFs composite nanofibers with confinement effect enhancing sodium storage performance - Huayu Wu; Mohan Yue; Lin He; Miao Zhang; Yimin Huang; Chang Sun; Yu Liu; Jindi Wang; Rongguan Lv; Rong Xing (Chemical Engineering Journal, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

A Study on the Extraction of Satellite Image Information for Two Types of Coastal Fishery Facility Fish Cages and Rafts Influenced by Clouds and Vessels - Ao Chen; Jialu Yu; Junbo Zhang; Gangyi Yu; Rong Wan (Journal of Marine Science and Engineering, 2024)
Research on the extraction of satellite information for the areas of coastal fish cages and rafts is important to quickly grasp the pattern and structure of the coastal fishery aquaculture industry. This study proposes a multi-feature and rule-based object-oriented image classification (MROIC) model, integrating spatial-spectral enhancement techniques with object-based image analysis classification methods. The MROIC model enhances spectral information by constructing ratio bands alongside principal component analysis, subsequently employing rule sets, edge detection algorithms, and comprehensive algorithmic merging techniques. It is applicable to satellite image classification tasks in complex environments, including influence of clouds and vessels. The information of fish cage and raft facilities is extracted via the MROIC model on the southwest coast of Xiapu County, Fujian Province, as an example. The results showed that the MROIC model attained an average total classification accuracy of 90.43% and a Kappa coefficient of 0.80. Extracting the area of fisheries facilities under the influence of clouds and vessels can provide better extraction accuracy and lower omission error. The MROIC model proposed in this study demonstrates high extraction accuracy and strong applicability, offering technical support for government planning in fishery facility areas and aiding in the risk assessment and management efficiency of fishery facility insurance.

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Precipitation patterns strongly affect vertical migration and methylation of mercury in legacy contaminated sites - Xujun Liang; Zhi-Cheng Hu; Yu-Rong Liu; Cunbin Gao; Yi Zhang; Yun-Yun Hao; Lijie Zhang; Jiating Zhao; Lizhong Zhu (Water Research, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Recycle of residual ammonium from weathered crust elution-deposited rare earth tailings via an efficient combined method of elution, struvite precipitation and on-line adsorption - Kejia Wu; Junxia Yu; Jia Wang; Xiaodi Li; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Journal of Water Process Engineering, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Strong electronic interaction in chromium-molybdenum dual incorporated few-layer cobalt sulfide nanosheets with lattice distortion for efficient bifunctional water splitting - Shi-Yu Lu; Wenzhao Dou; Chunjie Wu; Jun Zhang; Ling Wang; Tingting Hu; Rong Wang; Yin Liu; Qian Yang; Meng Jin (Fuel, 2024)

Research advances in technologies and mechanisms to regulate vinegar flavor - Zhankai Zhang; Zhi-hong Zhang; Ronghai He; Guozhong Zhao; Yongjian Yu; Rong Zhang; Xianli Gao (Food Chemistry, 2024)

Effect of solution plasma process on microorganism sterilization, physicochemical properties and nutrients of milk - Haifeng Rong; Yang Yu; Baiqing Zhang; Dongbing Tao; Tingyu Zhu; Dongge Wu; Fengming Ma (Food Chemistry, 2024)

Responses of yield, CH4 and N2O emissions to ratoon rice cropping and different management practices - Haiyang Yu; Rong Zhu; Xuechen Zhang; Xiangtian Meng; Chao Kong; Guangbin Zhang; Xinhui Liu; Yaying Li; Yongxiang Yu; Huaiying Yao (Field Crops Research, 2024)

MOF-derived S, N co-doped porous carbon matrix with single Fe atoms and CoSx nanoparticles dual-sites for enhanced oxygen reduction - Yu chen; Jian Rong; Jing Wu; Yuzhe Zhang; Huaisheng Ao; Xudong Zheng; Chao Jing; Ruilan Yang; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Representing ocean biology-induced heating effects in ROMS-based simulations for the Indo-Pacific Ocean - Wenzhe Zhang; Chuan Gao; Feng Tian; Yang Yu; Hongna Wang; Rong-Hua Zhang (Frontiers in Marine Science, 2024)
Incident shortwave radiation can penetrate and heat the upper ocean water column, acting to modulate the stratification, vertical mixing and sea surface temperature. As a light-absorbing constituent, ocean chlorophyll (CHL) plays an important role in regulating these processes; however, its heating effect on the ocean state remains controversial and exhibits strong model dependence on ways the solar radiation transmission and the related CHL-induced heating are represented. In this study, we implement a chlorophyll-based two-way coupling between physical and ecological processes within the Regional Ocean Modeling System (ROMS). The bio-physics coupled model performs well in simulating the structure and variability of oceanic physical and ecological fields in the tropical Indo-Pacific region. Three CHL-related heating terms are analyzed based on the model output to diagnose the ocean biology-induced heating effects, namely the shortwave radiation part penetrating out of the base of the mixed layer (ML; Q pen ), the portion absorbed within the ML ( Q abs ), and the rate of temperature change of the ML resulting from the Q abs effects ( R sr ). Results show that the spatio-temporal distributions of the three heating terms are mainly determined by the ML depth (MLD). However, Q pen can also be regulated by the euphotic depth (ED), especially in the western-central equatorial Pacific. This moderating effect is particularly evident during El Niño when the ED tends to be greater than the MLD; positive ED anomalies act to enhance the positive Q pen anomalies caused by negative MLD anomalies. For the first time, the bio-heating effects are quantified within the ROMS-based two-way coupling context between the physical submodel and ecological submodel over the tropical Indo-Pacific Ocean, providing a basis for further understanding of the bio-effects and mechanisms. It is expected that the methodology and understanding developed in this study can help explore the chlorophyll-related processes in the ocean and the interactions with the atmosphere.

Rhodamine and related substances in food: Recent updates on pretreatment and analysis methods - Rong-zhu Du; Yuan Zhang; Yu Bian; Chun-yu Yang; Xue-song Feng; Zhen-wei He (Food Chemistry, 2024)

Pesticide metabolite 3, 5, 6-trichloro-2-pyridinol causes massive damage to the cochlea resulting in hearing loss in adult mice - Mao Huang; Shuangshuang Mao; Yunfei Pan; Ziying Zhang; Fei Gui; Xiaohua Tan; Yu Hong; Rong Chen (Environmental Pollution, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Differential response of soil bacteria and fungi to carbon and respiration components in abandoned grasslands on the Loess Plateau, China - Xingfang Tian; Ying Zhang; Yujie Liang; Rong Fu; Lin Sun; Zhouchang Yu; Jiayi Shi; Ahejiang Sailike; Hongjian Hao; Wei Zhang (Plant and Soil, 2024)

Impact of a Potent Strain of Plant Growth-Promoting Bacteria (PGPB), Bacillus subtilis S1 on Bacterial Community Composition, Enzymatic Activity, and Nitrogen Content in Cucumber Rhizosphere Soils - Meng-Ting Zhang; Yu-Qing Bao; Bao-Yun Feng; Lu-Rong Xu; Ya-Ting Zhang; Er-Xing Wang; Yun-Peng Chen (Current Microbiology, 2024)

Long-term stationary fertilization decreased soil health in field-grown sweetpotato by increasing soil-borne diseases or allelochemicals - Xiaoya Zhu; Peng Zhao; Jing Wang; Qiangqiang Zhang; Yongchao Yu; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2024)

Assessing the potential of mariculture to provide ecosystem services based on cultured species, modes and regions - Yazhou Tang; Yu Tang; Rong Chen; Linyuan Chen; Dan Zhou; Jianhui Xue; Yongbo Wu; Yinlong Zhang (Ocean & Coastal Management, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Modeling of activated carbon and multi-scale molecular simulation of its water vapor adsorption: A review - Zhongfan Mo; Ming Li; Shengnan Sun; Rong Zhu; Danya Zhan; Aimin Li; Yinning Li; Ying Zhang; Qiongfen Yu (Journal of Environmental Chemical Engineering, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Macroaggregate is crucial in soil carbon and nitrogen accumulation under different vegetation types in the Loess Plateau, China - Hongjian Hao; Yujie Liang; Duo Pian; Ying Zhang; Yaxian Chen; Hongtao Lai; Zhouchang Yu; Ahejiang Sailike; Rong Wang; Ling Cao; Xinhui Han; Wei Zhang (Forest Ecology and Management, 2024)

PoIL8-L, a teleost interleukin-8 like, enhances leukocyte cellular vitality and host defense against bacterial infections in Japanese flounder (Paralichthys olivaceus) - Kun-yu Zhao; Yue Fang; Rong-jing Xu; Jian Zhang; Bin Sun; Xue-peng Li (Fish & Shellfish Immunology, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Enhanced antifouling behavior and phosphorus removal in a gravity-driven electrochemical dynamic membrane bioreactor (EDMBR) process: Performance and mechanisms - Yisong Hu; Lulu Zha; Luhe Tang; Jingyu Zhang; Weihang Deng; Yuan Yang; Zhenzhen Yu; Rong Chen (Chemical Engineering Journal, 2024)

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

The immunoadjuvant effects of interleukin-8 on Aeromonas veronii inactivated vaccine in largemouth bass (Micropterus salmoides) - Shun Yang; Qian-Rong Liang; Dao-Le Liu; Ze-Sheng Zhang; Yu-Hong Yang; Xiao-Fei Yao; Hui Fei (Aquaculture International, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

Advances in treatment technologies for silver-containing wastewater - Heng Yu; Hongliang Zhang; Chenyang Zhang; Rong Wang; Siyuan Liu; Ronghao Du; Wei Sun (Chemical Engineering Journal, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Self-heating photothermal synergistic catalytic decomposition of carcinogenic formaldehyde by α-MnO2 at ambient temperature: Functional roles of surface acidic-basic sites - Danni Ding; Zeyi Cheng; Yu Zhou; Nan Zhang; Wang Ran; Shaopeng Rong (Journal of Environmental Chemical Engineering, 2024)

In-situ electric swing adsorption enabling superior water vapor capture of salt-based carbon fibers - Rong Zhu; Yaowei Huang; Qiongfen Yu; Ming Li; Yunfeng Wang; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

The role of a novel secretory peptidoglycan recognition protein with antibacterial ability from the Chinese Oak Silkworm Antheraea pernyi in humoral immunity - Xutong Duan; Ting Fu; Chang Liu; Fuhui Wang; Chengbao Liu; Lin Zhao; JinZhu Yu; Xialu Wang; Rong Zhang (Insect Biochemistry and Molecular Biology, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Organic substitution regime with optimized irrigation improves potato water and nitrogen use efficiency by regulating soil chemical properties rather than microflora structure - Xiya Wang; Binggeng Yang; Lingling Jiang; Shicheng Zhao; Mengjiao Liu; Xinpeng Xu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Field Crops Research, 2024)

Dynamic processes of positive/negative immune-vascular crosstalk loop via functional MRI-guided monitor - Rong Zhang; Teng Jin; Yue Zhang; Xueqing Sui; Shiman Wu; Yue Wu; Dapeng Hao; Zhenwei Yao; Zhengze Yu; Xuejun Liu; Hua Zhang (Chemical Engineering Journal, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

First outbreak of trypanosomiasis in farmed blood parrot cichlids (Vieja melanura♀ × Amphilophus citrinellus♂) from southern China - Jun-Yu (俊余) Zhou (周); Liwen (力文) Xu (徐); Ying-Xin (潆心) Bi (毕); Jinyong (晋勇) Zhang (章); Geoff Hide; De-Hua (德华) Lai (赖); Zhao-Rong (照荣) Lun (伦) (Aquaculture, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

Efficient removal of the residual ammonium from weathered crust elution-deposited rare earth tailings by a ternary compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Rong Wang; Fang Zhou; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2024)

Strong ground motion characteristics of the 2022 MW 6.6 Luding earthquake and regional variability in ground motion among three earthquake areas in Sichuan, Southwest China - Bin Zhang; Xiaojun Li; Yanxiang Yu; Xiaojian Lu; Mianshui Rong; Su Chen; Zhao An; Zhenghui Xiong (Bulletin of Earthquake Engineering, 2024)

Numerical Modelling of the Hydrodynamic Performance of Biodegradable Drifting Fish Aggregating Devices in Currents - Tongzheng Zhang; Junbo Zhang; Qinglian Hou; Gangyi Yu; Ao Chen; Zhiqiang Liu; Rong Wan (Journal of Marine Science and Engineering, 2024)
Fish Aggregating Devices (FADs) are essential supplementary structures used in tropical tuna purse-seine fishing. They are strategically placed to attract tuna species and enhance fishing productivity. The hydrodynamic performance of FADs has a direct effect on their structural and environmental safety in the harsh marine environment. Conventional FADs are composed of materials that do not break down naturally, leading to the accumulation of waste in the ocean and potential negative effects on marine ecosystems. Therefore, this work aimed to examine the hydrodynamic performance of biodegradable drifting FADs (Bio-DFADs) in oceanic currents by numerical modelling. The Reynolds-averaged Navier–Stokes equation was used to solve the flow field and discretized based on the realizable k-ε turbulence model, employing the finite volume method. A set of Bio-DFADs was developed to assess the hydrodynamic performance under varying current velocities and attack angles, as well as different balsa wood diameters and sinker weights. The results indicated that the relative current velocity significantly affected the relative velocity of Bio-DFADs. The relative length of the raft significantly affected both the relative velocity and the relative wetted area in a pure stream. Finally, the diameter of the balsa wood affected the drift velocity, and the sinker’s relative weight affected the hydrodynamic performance of the Bio-DFADs.

A polyfunctionalized carbon framework composite for efficient decontamination of Cr(VI) and polycyclic aromatic nitrides from acidic wastewater - Weilong Wu; Han Zhang; Rong Qian; Kunru Yu; Ronghua Li; Kuok Ho Daniel Tang; Xuan Wu; Zhiqiang Guo; Cong Shao; Feixue Yue; Zengqiang Zhang (Environmental Science and Pollution Research, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Multistage dolomitization influenced by the Emeishan large igneous province: Petrographical and geochemical evidence - Yang Li; Xiyan Yang; Xinzhi Wang; Cunhui Fan; Xiangyu Fan; Yu Zhang; Rong Yang; Yue Li; Zisang Huang; Fei Huo (Marine and Petroleum Geology, 2024)

The degradation and antioxidant capacity of anthocyanins from eggplant peels in the context of complex food system under thermal processing - Zhiyue Wang; Yanfei Zhang; Zhijun Tu; Chengwei Yu; Rong Liu; Zeyuan Deng; Ting Luo (Food Bioscience, 2024)

Prospective findings from the Dongfeng-Tongji cohort: Exposure to various metals, the expression of microRNA-4286, and the incidence of acute coronary syndrome - Miaoyan Shen; Xuedan Xu; Wending Li; Xi Wang; Rong Peng; Xuezhen Liu; Qiuhong Wang; Xiaomin You; Pinpin Long; Hao Wang; Rundong Niu; Yu Yin; et al. (Environmental Research, 2024)

A methodological review of compound-specific radiocarbon analysis for polycyclic aromatic hydrocarbons in environmental matrices - Yu Fu; Rui Zhang; Shaopeng Rong; Yuling Wu; Ying Wu; Miaolei Ya (Environmental Pollution, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

Structural elucidation a complex galactosyl and glucosyl-rich pectin from the pericarp of immature fruits of Juglans mandshurica Maxim. - Xi-Zhe Sun; Qing-Yu Zhang; Si-Liang Jiang; Rong-Jian Zhu; Jun-Hong Chai; Jun Liang; Hai-Xue Kuang; Yong-Gang Xia (Glycoconjugate Journal, 2024)

Tracking diarrhea viruses and mpox virus using the wastewater surveillance network in Hong Kong - Xiawan Zheng; Keyue Zhao; Bingjie Xue; Yu Deng; Xiaoqing Xu; Weifu Yan; Chao Rong; Kathy Leung; Joseph T. Wu; Gabriel M. Leung; Malik Peiris; Leo L.M. Poon; et al. (Water Research, 2024)

Piped-slow-release calcium nitrate dosing: A new approach to in-situ sediment odor control in rural areas - Yongchun Zhang; Ziyang Liang; Peiling Li; Jiangtian Lai; Peilun Kang; Rong Huang; Yuhai Liang; Guangwei Yu (Science of The Total Environment, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

A new 1,4-benzoxazine derivative produced by endophytic Colletotrichum gloeosporioides B-142 - Bing Zhang; Zhi-pu Huang; Yu Si; Ke-tao Zhang; Xiao-rong Xu; Jian-hong Chen; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2024)

Collaborative Q-learning hyper-heuristic evolutionary algorithm for the production and transportation integrated scheduling of silicon electrodes - Rong Hu; Yu-Fang Huang; Xing Wu; Bin Qian; Ling Wang; Zi-Qi Zhang (Swarm and Evolutionary Computation, 2024)

Use of machine learning to identify key factors regulating volatilization of semi-volatile organic chemicals from soil to air - Rong Wang; Kai-Hui Zhang; Yu Wang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Science of The Total Environment, 2024)

Electrospinning-assisted construction of rapid proton conduction channels in halloysite nanotube-encapsulated ionic liquid-embedded sulfonated poly(ether ether ketone) proton exchange membranes - Chunyong Xiong; Zhiwei Ling; Bei Wang; Yang Yu; Qingting Liu; Xudong Fu; Chonggang Wu; Rong Zhang; Shengfei Hu; Xujin Bao; Jun Yang (Fuel, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Biochar-mediated synergistic promotion of DIET and IHT: Kinetic and thermodynamic insights into propionate two-step syntrophic methanogenesis - Danyang Zhao; Peiyun Zhang; Yaqian Liu; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

A green and eco-friendly method to enhance Bamboo flame resistance via calcium alginate assisted in-situ mineralization of hydroxyapatite - Lu He; Gege Bao; Xi Yu; Xiaofeng Zhang; Xiaobei Jin; Zixuan Yu; Ying He; Rong Zhang; Daochun Qin (Chemical Engineering Journal, 2024)

Early warning of urban heavy metal pollution based on PMF- MeteoInfo model combined with physicochemical properties of dust - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Xinying Zhang; Wei Yu; Rong Yu; Xinyu Liu (Stochastic Environmental Research and Risk Assessment, 2024)

Population pharmacokinetics and pharmacodynamics of efmarodocokin alfa (IL-22Fc) - Yanke Yu; Michael E. Rothenberg; Han Ting Ding; Ari Brekkan; Gizette Sperinde; Brandon Harder; Rong Zhang; Ryan Owen; Nastya Kassir; Annemarie N. Lekkerkerker (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

Response of soil microbial properties in the life cycle of potatoes to organic substitution regimes in North China - Xiya Wang; Shicheng Zhao; Xinpeng Xu; Mengjiao Liu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Soil and Tillage Research, 2024)

Impacts of polypropylene microplastics on the distribution of cadmium, enzyme activities, and bacterial community in black soil at the aggregate level - Quan-Ying Wang; Qi-Rong Wang; Tian-Ye Wang; Shao-Qing Zhang; Hong-Wen Yu (Science of The Total Environment, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Fe(III) oxyhydroxides mediated electron transfer from thiols to O2 for hydroxyl radical production - Peng Zhang; Wanyun Zhang; Hao Yu; Rong Chen; Yiran Liu; Yingxiao Tian; Songhu Yuan (Chemical Geology, 2024)

Fine-grained PM 2 . 5 prediction in Lanzhou based on the spatiotemporal graph convolutional network - Qiang Zhang; Xin Yu; Rong Guo; Yibin Qiao; Ying Qi (Atmospheric Pollution Research, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

27-Hydroxycholesterol inhibits trophoblast fusion during placenta development by activating PI3K/AKT/mTOR signaling pathway - Xiaoyan Zhao; Xiaxia Cai; Haiyan Zhu; Qinyu Dang; Qian Yang; Yandi Zhu; Yadi Zhang; Mengling Zhang; Xinyin Jiang; Zhuo Hu; Yuchen Wei; Rong Xiao; et al. (Archives of Toxicology, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

Effects of zinc oxide nanocomposites on microorganism growth and protection of physicochemical quality during maize storage - Dong-Dong Zhang; Jin-Feng Zhao; Li-Qin Tan; Qiong Wu; Hao-Xin Lv; Yu-Rong Zhang; Min Zhang (International Journal of Food Microbiology, 2024)

A study of volatiles of young citrus fruits from four areas based on GC–MS and flash GC e-nose combined with multivariate algorithms - Qian Zhang; Rong Xue; Xi Mei; Lianlin Su; Wei Zhang; Yu Li; Jinguo Xu; Jing Mao; Chunqin Mao; Tulin Lu (Food Research International, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Introducing local-molecule trap in a cost-effective metal–organic framework for C2H2/CO2 separation - Xue-Qian Wu; Tao He; Peng-Dan Zhang; Jiamei Yu; Jian-Rong Li (Chemical Engineering Journal, 2024)

Subchannel thermal–hydraulic analysis of a wire-wrapped 19-pin rod bundle in the NACIE-UP facility - Rong Zhang; Dalin Zhang; Yu Liang; Jinshun Wang; Jian Deng; Xisi Zhang; Zhixin Niu; Wenxi Tian; Suizheng Qiu; Qi Luo (Annals of Nuclear Energy, 2024)

Review of the Accuracy of Satellite Remote Sensing Techniques in Identifying Coastal Aquaculture Facilities - Ao Chen; Zehua Lv; Junbo Zhang; Gangyi Yu; Rong Wan (Fishes, 2024)
The predominant form of aquaculture is the facility fishery, which is also subject to significant impacts from marine disasters. Conducting research on the extraction of facility fishery areas based on remote sensing technology is crucial to efficiently comprehending the configuration of coastal culture patterns and to establishing scientifically sound plans for managing and administering these areas. The extensive dispersion of facility fishery areas in coastal regions poses a challenge to the conduction of comprehensive field surveys. The utilization of satellite remote sensing images for information extraction has emerged as a significant area of research in the fields of coastal fishery and ecological environment. This study provides a systematic description of the current research status of coastal fishery area extraction methods using remote sensing technology from 2000 to 2022 reported in the literature. The methods discussed include the visual interpretation method, image element-based classification, object-based classification, supervised classification, unsupervised classification, and neural network classification. The extraction accuracy of each method in the coastal facility fishery area is evaluated, and the advantages and disadvantages of these methods, as well as their limitations and existing problems, are analyzed in detail, to construct a reference framework for the investigation of the high-precision extraction of facility fishery areas from satellite remote sensing images.

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Insights into current bio-processes and future perspectives of carbon-neutral treatment of industrial organic wastewater: A critical review - Xinzheng Zhang; Yuqin Fan; Tianwei Hao; Rong Chen; Tao Zhang; Yong Hu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Transpiration-mimicking wood-based microfluidic aluminum-air batteries: Green power sources for miniaturized applications - Wei Wang; Liu-Liu Shen; Peiran Wu; Hui Yu; Jiansong Wang; Yipu Xu; Xiangzun Dong; Xuanxuan Cui; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2024)

Ethane-selective permeation in mixed matrix membranes containing fluorinated carboxylic acid functionalized metal-organic frameworks - Yuxiu Sun; Qianqian Yu; Chenxu Geng; Gui-Rong Zhang; Zhengqing Zhang; Zhihua Qiao; Chongli Zhong (Chemical Engineering Journal, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Evaluation of the ecohydrological separation of different geomorphological units in a semi-arid area - Yu Zhang; Mingjun Zhang; Yuquan Qiang; Jiaxin Wang; Rong Guo; Deye Qu; Shengjie Wang (Applied Geochemistry, 2024)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Characterization of the aerosol vertical distributions and their impacts on warm clouds based on multi-year ARM observations - Yun Lin; Yoshihide Takano; Yu Gu; Yuan Wang; Shujun Zhou; Tianhao Zhang; Kuilin Zhu; Jingyu Wang; Bin Zhao; Gang Chen; Damao Zhang; Rong Fu; et al. (Science of The Total Environment, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Synergistic leaching process for ion-exchange ammonium from weathered crust elution deposited rare earth tailings with potassium magnesium compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Guoping Song; Ze Ouyang; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Environmental Science and Pollution Research, 2023)

Associations of exposure to bisphenol A and its substitutes with neurodevelopmental outcomes among infants at 12 months of age: A cross-sectional study - Zhuanning Xia; Cheng Lv; Yan Zhang; Rong Shi; Qi Lu; Ying Tian; Xiaoning Lei; Yu Gao (Chemosphere, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Enhancing simultaneous desulfurization and denitrification efficiency of cement kiln exhaust gas via co-catalytic Fenton oxidation process - Tongsheng Zhang; Hui Peng; Rong Chen; Yiqun Guo; Jiawei Wang; Xinzhi Chen; Jiangxiong Wei; Qijun Yu (Journal of Cleaner Production, 2023)

A new ground-motion model to predict horizontal PGA, PGV, and spectral acceleration for small-to-moderate earthquakes in the capital circle region of China - Bin Zhang; Xiaojun Li; Yanxiang Yu; Jize Sun; Mianshui Rong; Su Chen (Journal of Asian Earth Sciences, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Biochar facilitates methanogens evolution by enhancing extracellular electron transfer to boost anaerobic digestion of swine manure under ammonia stress - Gaojun Wang; Peng Fu; Bo Zhang; Ji Zhang; Qiuyi Huang; Gaofei Yao; Qian Li; Mawuli Dzakpasu; Jianfeng Zhang; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Fine mapping and candidate gene analysis of a novel fertility restorer gene for C-type cytoplasmic male sterility in maize (Zea mays L.) - Peng Zhang; Zhuofan Zhao; Mingmin Zheng; Yongming Liu; Qunkai Niu; Xiaowei Liu; Ziwen Shi; Hongyang Yi; Tao Yu; Tingzhao Rong; Moju Cao (Theoretical and Applied Genetics, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Revealing the hidden burden for lake management: the sediment phosphorus storage pools in Eastern Plain Lake Zone, China - Chenxue Zhang; Yanjie Zhao; Min Xu; Wenxiu Zheng; Yu Zhao; Bo Qin; Rong Wang (Environmental Science and Pollution Research, 2023)

Towards disentangling the classification of freshwater fish trypanosomes - Peng Zhang; Jie Liu; Xiao-Ming Yin; Jun-Yu Zhou; Julius Lukeš; Zhao-Rong Lun; De-Hua Lai (Marine Life Science & Technology, 2023)
Currently, new species of freshwater fish trypanosomes, which are economically important parasites, are being described based on subjectively selected features, i.e., their cell morphology and the host species. We have performed detailed phylogenetic and haplotype diversity analyses of all 18S rRNA genes available for freshwater fish trypanosomes, including the newly obtained sequences of Trypanosoma carassii and Trypanosoma danilewskyi . Based on a sequence similarity of 99.5%, we divide these trypanosomes into 15 operational taxonomic units, and propose three nominal scenarios for distinguishing T. carassii and other aquatic trypanosomes. We find evidences for the existence of a low number of freshwater fish trypanosomes, with T. carassii having the widest geographic and host ranges. Our analyses support the existence of an umbrella complex composed of T. carassii and two sister species.

Surface acidic sites strengthened core-shell HC@MnO2 for enhanced gaseous ammonia adsorption - Weijiang He; Jingling Lu; Nan Zhang; Yu Zhou; Danni Ding; Yanfang Feng; Shaopeng Rong (Chemosphere, 2023)

Characterization of nitrogen and phosphorus at the ice-water-sediment interface and the effect of their migration on overlying water quality in Daihai Lake (China) during the freezing period - Rong Wu; Yu Liu; Sheng Zhang; Xiaohong Shi; Shengnan Zhao; Junping Lu; Xueer Kang; Shihuan Wang; Yue Wu; Lauri Arvola (Science of The Total Environment, 2023)

Composition and sources of suspended particles in the Pacific Arctic region - Xiaoguo Yu; Liming Ye; Yeping Bian; Yanguang Liu; Weiyan Zhang; Weiguo Wang; Xuying Yao; Jihao Zhu; Xiaobing Jin; Rong Wang (Marine Environmental Research, 2023)

Application of super-cooled storage of aquatic products: A review - Xin-Yu Liu; Xue-Lai Zhang; Guan-Bang Wang; Fan-Yang Mo; Xin-Rong Zhang (International Journal of Refrigeration, 2023)

Experimental investigation of combustion and ash deposition characteristics of coal-NH3 cofiring in a 200 kW furnace - Shihao Hu; Yize Zhang; Yuguo Ni; Xinfeng Yu; Yan Rong; Kefa Cen; Hao Zhou (Fuel, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Effects of nano-silicon dioxide on minerals, antioxidant enzymes, and growth in bitter gourd seedlings under cadmium stress - Hongyan Sun; Bo Zhang; Zhijiang Rong; Songjie He; Yifan Gao; Jia Yu; Qingmei Zhang (Acta Physiologiae Plantarum, 2023)

Exploration for cobalt/nitrogen-doped catalyst to creatinine degradation via peroxymonosulfate activation: toxicity evaluation, statistical modeling, and mechanisms study - Jiadi Liu; Yawen Dong; Yu Kang; Qian Kong; Kuaibing Wang; Feifei Mao; Yuanqing Bu; Rong Zhou; Chunyong Zhang; Hua Wu (Environmental Science and Pollution Research, 2023)

Emergence of the clinical rdar morphotype carbapenem-resistant and hypervirulent Klebsiella pneumoniae with enhanced adaption to hospital environment - Congcong Liu; Ning Dong; Xueting Huang; Zixian Huang; Chang Cai; Jiayue Lu; Hongwei Zhou; Jingren Zhang; Yu Zeng; Fan Yang; Gongxiang Chen; Zhangqi Shen; et al. (Science of The Total Environment, 2023)

Direct discharge of sewage to natural water through illicitly connected urban stormwater systems: An overlooked source of dissolved organic matter - Ruihua Zhang; Rong Xiao; Feifei Wang; Wenhai Chu; Jinglong Hu; Yu Zhang; Wei Jin; Jan Peter van der Hoek; Zuxin Xu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

How to improve pollutant emission performances of household biomass cookstoves: A review - Mengsi Deng; Pengxin Zhang; Yazhou Nie; Yu Shi; Hanyu Yang; Dan Wu; Xing Rong; Rongjiang Ma (Energy and Buildings, 2023)

Solvent-freely polymerizing catechol and paraformaldehyde to nitrogen-rich carbon for high-volumetric-performance supercapacitor - Yushuai Yao; Rong Zhou; Yi Yu; Jian Chen; Cheng Du; Yan Zhang; Tao Long; Liu Wan; Qiuyue Wang; Mingjiang Xie (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Treatment of fresh leachate by anaerobic membrane bioreactor: On-site investigation, long-term performance and response of microbial community - Weifu Yan; Yulin Wang; Yemei Li; Chao Rong; Dou Wang; Chunxiao Wang; Yubo Wang; Yee-lok Yuen; Fanny Fong Wong; Ho-Kwong Chui; Yu-You Li; Tong Zhang (Bioresource Technology, 2023)

Effects of Long-term Non-application of Phosphorus Fertilizer on Bacterial Community Structure and Metabolite Profiles of Sweetpotato Rhizosphere - Xiaoya Zhu; Jing Wang; Qiangqiang Zhang; Peng Zhao; Ming Liu; Rong Jin; Yongchao Yu; Aijun Zhang; Zhonghou Tang (Journal of Soil Science and Plant Nutrition, 2023)

Relationship between daily variations of methane emissions and eructation peaks in dairy cows measured with an automated head-chamber system - Rong Wang; Yu Rong Cao; Xiu Min Zhang; Fan Zhang; Xu Tian; Rong Zhen Zhong; Zhi Liang Tan; Min Wang (Animal Feed Science and Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Dietary selenium requirement for on-growing grass carp, Ctenopharyngodon idellus - Feifei Chen; Ziyi Zhang; Li Wang; Haodong Yu; Xuezhen Zhang; Keming Rong (Aquaculture, 2023)

Method for quantitative extraction of copper hydroxide nanoparticles from farmland soil - Xin-Yuan Li; Yuan Yang; Peng Huang; Ying-Rong Wang; Yu-Lin Nie; Li Zhang; Qiang Wang (Science of The Total Environment, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

A deep spatio-temporal learning network for continuous citywide air quality forecast based on dense monitoring data - Rong Guo; Qiang Zhang; Xin Yu; Ying Qi; Bu Zhao (Journal of Cleaner Production, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

The role of GATA switch in benzene metabolite hydroquinone inhibiting erythroid differentiation in K562 cells - Chun-Hong Yu; Shui-Qing Yang; Yu-Jing Zhang; Long Rong; Zong-Chun Yi (Archives of Toxicology, 2023)

Climatic seasonality challenges the stability of microbial‐driven deep soil carbon accumulation across China - Shuhai Wen; Jiaying Chen; Ziming Yang; Lei Deng; Jiao Feng; Wen Zhang; Xiao‐Min Zeng; Qiaoyun Huang; Manuel Delgado‐Baquerizo; Yu‐Rong Liu (Global Change Biology, 2023)
Microbial residues contribute to the long‐term stabilization of carbon in the entire soil profile, helping to regulate the climate of the planet; however, how sensitive these residues are to climatic seasonality remains virtually unknown, especially for deep soils across environmental gradients. Here, we investigated the changes of microbial residues along soil profiles (0–100 cm) from 44 typical ecosystems with a wide range of climates (~3100 km transects across China). Our results showed that microbial residues account for a larger portion of soil carbon in deeper (60–100 cm) vs. shallower (0–30 and 30–60 cm) soils. Moreover, we find that climate especially challenges the accumulation of microbial residues in deep soils, while soil properties and climate share their roles in controlling the residue accumulation in surface soils. Climatic seasonality, including positive correlations with summer precipitation and maximum monthly precipitation, as well as negative correlations with temperature annual range, are important factors explaining microbial residue accumulation in deep soils across China. In particular, summer precipitation is the key regulator of microbial‐driven carbon stability in deep soils, which has 37.2% of relative independent effects on deep‐soil microbial residue accumulation. Our work provides novel insights into the importance of climatic seasonality in driving the stabilization of microbial residues in deep soils, challenging the idea that deep soils as long‐term carbon reservoirs can buffer climate change.

A new δ-valerolactone produced by marine Streptomyces sp. YIM 13591 - Bing Zhang; Yu-ying Zhao; Zhi-pu Huang; Ke-tao Zhang; Xiao-rong Xu; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Effect of flue gas components on the removal of cadmium pollutants by transition metal-modified activated carbon: Density functional theory and thermodynamic study - Xin-Yue Zhou; Jia-Le Zhou; Rong Guo; Yin-jie Liu; Yi-fei Yu; Bing Zhang; Yang-Wen Wu; Li Zhao; Qiang Lu (Fuel, 2023)

Constructing electron transport channels in FeSe2 microspheres by a facile strategy for superior long-life and ultrafast sodium-ion storage - Ming Xu; Yu Ma; Rong Liu; Huanhao Xiao; Liming Chen; Ziqiang Zhang; Lei Wang; Guohui Yuan (Chemical Engineering Journal, 2023)

Asymmetry of Salinity Variability in the Tropical Pacific during Interdecadal Pacific Oscillation Phases - Hai Zhi; Zihui Yang; Rong-Hua Zhang; Pengfei Lin; Jifeng Qi; Yu Huang; Meng Dong (Advances in Atmospheric Sciences, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Urban particulate water-soluble organic matter in winter: Size-resolved molecular characterization, role of the S-containing compounds on haze formation - Cuiping Ning; Yuan Gao; Haijun Zhang; Haoran Yu; Rong Cao; Jiping Chen (Science of The Total Environment, 2023)

Chemical weathering in the Himalayan system in response to the evolution of the Indian summer monsoon since 37 ka - Long Tan; Jianguo Liu; Yun Huang; Rong Xiang; Shengfa Liu; Hui Zhang; Jingrui Li; Linghui Yu; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Urinary neonicotinoid insecticides and adiposity measures among 7-year-old children in northern China: A cross-sectional study - Zhenping Lu; Yi Hu; Lap Ah Tse; Jinxia Yu; Zhuanning Xia; Xiaoning Lei; Yan Zhang; Rong Shi; Ying Tian; Yu Gao (International Journal of Hygiene and Environmental Health, 2023)

Construction of α-MnO2/g-C3N4 Z-scheme heterojunction for photothermal synergistic catalytic decomposition of formaldehyde - Nan Zhang; Weijiang He; Zeyi Cheng; Jingling Lu; Yu Zhou; Danni Ding; Shaopeng Rong (Chemical Engineering Journal, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Responses of Bacillus sp. under Cu(II) stress in relation to extracellular polymeric substances and functional gene expression level - Ling-ling Wang; Zheng-yan Yin; Yun Xu; Miao-yu Deng; Kai-ming Zhang; Quan Wang; Rong-ping Chen; Lei Yu (Environmental Science and Pollution Research, 2023)

Corrigendum to ’ Biochar enhances the biotransformation of organic micropollutants (OMPs) in an anaerobic membrane bioreactor treating sewage’ [Water Research 223 (2022) 118974] - Zhen Lei; Shixin Zhang; Lianxu Wang; Qian Li; Yu-You Li; Xiaochang C. Wang; Rong Chen (Water Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Intensification of the East Asian winter monsoon resulted in greater preservation of terrestrial organic carbon on the inner shelf of the East China Sea since the last 1400 years - Shuai Liu; Da-Wei Li; Rong Xiang; Meng Yu; Hailong Zhang; Li Li; Meixun Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Enhancement of acidic sites in layered MnO2 for the highly efficient selective catalytic oxidation of gaseous ammonia - Yu Zhou; Shaopeng Rong; Huifang Xie; Yanfang Feng; Danni Ding; Weijiang He; Nan Zhang; Jingling Lu (Journal of Environmental Chemical Engineering, 2023)

Purple red rice bran anthocyanins reduce the digestibility of rice starch by forming V-type inclusion complexes - Weidong Zhang; Haibin Zhu; Liyuan Rong; Yi Chen; Qiang Yu; Mingyue Shen; Jianhua Xie (Food Research International, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Detection and Identification of Fish Skin Health Status Referring to Four Common Diseases Based on Improved YOLOv4 Model - Gangyi Yu; Junbo Zhang; Ao Chen; Rong Wan (Fishes, 2023)
A primary problem affecting the sustainable development of aquaculture is fish skin diseases. In order to prevent the outbreak of fish diseases and to provide prompt treatment to avoid mass mortality of fish, it is essential to detect and identify skin diseases immediately. Based on the YOLOv4 model, coupled with lightweight depthwise separable convolution and optimized feature extraction network and activation function, the detection and identification model of fish skin disease is constructed in this study. The developed model is tested for the diseases hemorrhagic septicemia, saprolegniasis, benedeniasis, and scuticociliatosis, and applied to monitor the health condition of fish skin in deep-sea cage culture. Results show that the MobileNet3-GELU-YOLOv4 model proposed in this study has an improved learning ability, and the number of model parameters is reduced. Compared to the original YOLOv4 model, its mAP and detection speed increased by 12.39% and 19.31 FPS, respectively. The advantages of the model are its intra-species classification capability, lightweight deployment, detection accuracy, and speed, making the model more applicable to the real-time monitoring of fish skin health in a deep-sea aquaculture environment.

Genome-wide DNA methylation and transcription analysis reveal the potential epigenetic mechanism of heat stress response in the sea cucumber Apostichopus japonicus - Mengyang Chang; Jianlong Ge; Meijie Liao; Xiaojun Rong; Yingeng Wang; Bin Li; Xinrong Li; Jinjin Wang; Zheng Zhang; Yongxiang Yu; Chunyuan Wang (Frontiers in Marine Science, 2023)
DNA methylation is an important epigenetic modification that regulates many biological processes. The sea cucumber Apostichopus japonicus often suffers from heat stress that affects its growth and leads to significant economic losses. In this study, the mRNA expression patterns and DNA methylation characteristics in the body wall of A. japonicus under heat stress were analyzed by whole-genome bisulfite sequencing (WGBS) and transcriptome sequencing (RNA-seq). We found that CpG was the main DNA methylation type, and heat stress caused a significant increase in the overall methylation level and methylation rate, especially in the intergenic region of the A. japonicus genome. In total, 1,409 differentially expressed genes (DEGs) and 17,927 differentially methylated genes (DMGs) were obtained by RNA-seq and WGBS, respectively. Association analysis between DNA methylation and transcription identified 569 negatively correlated genes in both DMGs and DEGs, which indicated that DNA methylation affects on transcriptional regulation in response to heat stress. These negatively correlated genes were significantly enriched in pathways related to energy metabolism and immunoregulation, such as the thyroid hormone signaling pathway, renin secretion, notch signaling pathway and microRNAs in cancer. In addition, potential key genes, including heat shock protein ( hsp70 ), calcium-activated chloride channel regulator 1( clca1 ), and tenascin R ( tnr ), were obtained and their expression and methylation were preliminarily verified. The results provide a new perspective for epigenetic and transcriptomic studies of A. japonicus response to heat stress, and provide a reference for breeding sea cucumbers resistant to high temperatures.

Efficient inactivation of the contamination with pathogenic microorganisms by a combination of water spray and plasma-activated air - Li Guo; Pengyu Zhao; Yikang Jia; Tianhui Li; Lingling Huang; Zifeng Wang; Dingxin Liu; Zhanwu Hou; Yizhen Zhao; Lei Zhang; Hua Li; Yu Kong; et al. (Journal of Hazardous Materials, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Electrophilic components from Xiaoheiyao (rhizomes of Inula nervosa Wall.) alleviate the production of heterocyclic aromatic amines via creatinine inhibition - Xiang-Rong Cheng; Jia-Hui Ma; Issoufou Amadou; Wei Zhao; Yu-Yao Chen; Chen-Xi Zhang; Bin Guan (Food Chemistry, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

The Structure and Function of Glial Networks: Beyond the Neuronal Connections - Hai-Rong Peng; Yu-Kai Zhang; Jia-Wei Zhou (Neuroscience Bulletin, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Density estimation method of mature wheat based on point cloud segmentation and clustering - Rong Zou; Yu Zhang; Jin Chen; Jinyan Li; Wenjie Dai; Senlin Mu (Computers and Electronics in Agriculture, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

The emergence of novel macrolide resistance island in Macrococcus caseolyticus and Staphylococcus aureus of food origin - Feng Zhang; Shi Wu; Jingsha Dai; Jiahui Huang; Jumei Zhang; Miao Zhao; Dongli Rong; Yuanyu Li; Juan Wang; Moutong Chen; Liang Xue; Yu Ding; et al. (International Journal of Food Microbiology, 2023)

Diagnosis of atmospheric circulation shifts in the central Tibetan Plateau: Evidence from stable isotopes - Yao Li; Wusheng Yu; Lide Tian; Stephen Lewis; Kei Yoshimura; Cheng Wang; Jiangpeng Cui; Yaoming Ma; Rong Guo; Jingyi Zhang; Zhaowei Jing; Lili Shao; et al. (Atmospheric Research, 2023)

Construction, Characterization, and Application of an Ammonium Transporter (AmtB) Deletion Mutant of the Nitrogen-Fixing Bacterium Kosakonia radicincitans GXGL-4A in Cucumis sativus L. Seedlings - Yu-Qing Bao; Meng-Ting Zhang; Bao-Yun Feng; Wulale Jieensi; Yu Xu; Lu-Rong Xu; Ying-Ying Han; Yun-Peng Chen (Current Microbiology, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

A study on the correlation between intrauterine microbiota and uterine pyogenesis in dogs - Hui-Hua Zheng; Chong-Tao Du; Yu-Zhu Zhang; Chao Yu; Rong-Lei Huang; Xin-Yue Tang; Guang-Hong Xie (Theriogenology, 2023)

Effects of different pretreatment methods on drying kinetics, three-dimensional deformation, quality characteristics and microstructure of dried apple slices - Jun-Wen Bai; Lu Zhang; Joshua H. Aheto; Jian-Rong Cai; Yu-Chi Wang; Li Sun; Xiao-Yu Tian (Innovative Food Science & Emerging Technologies, 2023)

A novel core–shell structure of CuNW@PSS accelerates the process of methane hydrate formation - Wenlian Rong; Yu Zhang; Shengjun Luo; Rongbo Guo (Fuel, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

Deciphering the electronic-level mechanism of Na+ transport in a graphdiyne desalination membrane with periodic nanopores - Jiongjiong Xu; Kun Meng; Yutao Niu; Changhong Zhang; Kui Xu; Ju Rong; Yan Wei; Xiaohua Yu (Desalination, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

Spatiotemporal impacts of climate change and human activities on water resources and ecological sensitivity in the Mekong subregion in Cambodia - Yi Lin; Yu Rong; Lang Li; Fengting Li; Hanchao Zhang; Jie Yu (Environmental Science and Pollution Research, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Molecular Characterization and Dietary Regulation of Glutaminase 1 (gls1) in Triploid Crucian Carp (Carassius auratus) - Yangbo Xiao; Rong Huang; Shenping Cao; Dafang Zhao; Zhuangwen Mao; Chuchu Xiao; Zhehua Xu; Xiaomei Zhou; Xinran Zhang; Yu Zhang; Jianzhou Tang; Junyan Jin; et al. (Fishes, 2022)
Kidney-type glutaminase, encoded by the gls1 gene, plays a critical role in glutamate production and improvement of meat flavor. In this study, a gls1 gene encoding 595 amino acids was cloned from triploid crucian carp (Carassius auratus) (TCC) and showed a high similarity with the gls1 gene found in Cyprinus carpio, Sinocyclocheilus rhinocerous and Puntigrus tetrazona. Comparing the abundance of gls1 in different tissues, we found its expression level in the brain and liver were significantly higher than that in heart, gut, kidney, spleen and muscle. gls1 expression in the brain reached the highest value. In addition, the expression levels of gls1 also appeared different in diurnal variation, with the highest expression seen at 9:00, while it was low at 3:00, 6:00, 15:00 and 24:00. Furthermore, dietary regulation of gls1 expression was investigated in our study. In each feeding trial, each diet was randomly assigned to triplicate tanks. Fish were fed one of the tested diets up to satiation twice daily. The results showed that gls1 expression increased in 32% protein group and decreased in 35–41% protein group. The results of different protein source experiments showed that the expression of gls1 gene in the mixed protein group (the control group) was significantly higher than that in the fish meal and soybean meal groups. Glutamate treatment revealed that appropriate concentrations (0.10 mg/mL in vivo and 2.00% in vitro) of glutamate remarkably improved the expression of gls1. Besides, diets supplemented with 0.80–1.60% lysine-glutamate dipeptide exhibited a down regulatory impact on gls1 expression. In conclusion, this study demonstrated that the expression of gls1 in TCC was increased by 32% protein diet, mixed protein source diet and diet with 2.00% glutamate concentration, while decreased by 0.80–1.60% lysine-glutamate dipeptide. The findings of this study provide a reference for the regulation of gls1 and have a potential application in the optimization of dietary formula in aquaculture.

Plastid diversity and chromoplast biogenesis in differently coloured carrots: role of the DcOR3Leu gene - Yu-Min Zhang; Rong-Hua Wu; Lu Wang; Ya-Hui Wang; Hui Liu; Ai-Sheng Xiong; Zhi-Sheng Xu (Planta, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Local temperature increases reduce soil microbial residues and carbon stocks - Xiao‐Min Zeng; Jiao Feng; Dai‐Lin Yu; Shu‐Hai Wen; Qianggong Zhang; Qiaoyun Huang; Manuel Delgado‐Baquerizo; Yu‐Rong Liu (Global Change Biology, 2022)
Warming is known to reduce soil carbon (C) stocks by promoting microbial respiration, which is associated with the decomposition of microbial residue carbon (MRC). However, the relative contribution of MRC to soil organic carbon (SOC) across temperature gradients is poorly understood. Here, we investigated the contribution of MRC to SOC along two independent elevation gradients of our model system (i.e., the Tibetan Plateau and Shennongjia Mountain in China). Our results showed that local temperature increases were negatively correlated with MRC and SOC. Further analyses revealed that rising temperature reduced SOC via decreasing MRC, which helps to explain future reductions in SOC under climate warming. Our findings demonstrate that climate warming has the potential to reduce C sequestration by increasing the decomposition of MRC, exacerbating the positive feedback between rising temperature and CO 2 efflux. Our study also considered the influence of multiple environmental factors such as soil pH and moisture, which were more important in controlling SOC than microbial traits such as microbial life‐style strategies and metabolic efficiency. Together, our work suggests an important mechanism underlying long‐term soil C sequestration, which has important implications for the microbial‐mediated C process in the face of global climate change.

Preparation of Pinocembrin-Loaded F127/MPEG-PDLLA Polymer Micelles and Anti-Osteoporotic Activity - Xia Cao; Qing He; Michael Adu-Frimpong; Xinyi Shen; Wanjing Rong; Xiaoxiao Li; Jian Zhang; Xiaoli Xia; Feng Shi; Hao Ji; Elmurat Toreniyazov; Qilong Wang; et al. (AAPS PharmSciTech, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Physiology, metabolism, antibiotic resistance, and genetic diversity of Harveyi clade bacteria isolated from coastal mariculture system in China in the last two decades - Hao Kang; Yongxiang Yu; Meijie Liao; Yingeng Wang; Guanpin Yang; Zheng Zhang; Bin Li; Xiaojun Rong; Chunyuan Wang (Frontiers in Marine Science, 2022)
Vibrio bacteria, particularly members of the Harveyi clade, are the most important pathogens of aquatic organisms that cause significant economic losses in the world. It is difficult to provide specific data on taxa of the Harveyi clade for biological research and prevention strategies. Therefore, we conducted an extensive phenotypic and antibiotic resistance study, as well as phylogenetic and molecular typing of 192 isolates of the Harveyi clade collection from 2000 to 2020 with a typical interannual difference from a coastal area in China. The isolates had a significant interspecific genetic and antibiotic resistance diversity. Based on the multilocus sequence analysis (MLSA) of housekeeping genes ( gyrB , pyrH , recA , and atpA ), 192 Harveyi clade isolates were rapidly and accurately classified into 10 species. The population of these isolates was composed of 95 sequence types (STs), of which 92 STs were newly identified, indicating a high degree of genetic diversity. ST327 ranked first, accounting for 11.5% of the total number of isolates (22 out of 192), followed by ST215 with 6.25%, while 63 STs included single isolates. At the metabolic level, the physiological and biochemical experiments revealed that all the Harveyi clade isolates were positive for oxidase and negative for melibiose. The isolates showed a varied tolerance to 11 antibiotics. No isolates were resistant to neomycin. The percentages of sulfadimidine-resistant strains (61 out of 192), sulfadiazine (44 out of 192), sulfamonomethoxine (44 out of 192), sulfamethoxazole (33 out of 192), thiamphenicol (34 out of 192), ciprofloxacin (52 out of 192), and enrofloxacin (31 out of 192) were 31.77%, 22.92%, 22.92%, 17.19%, 17.71%, 27.08%, and 16.15%, respectively. A proportion of 61.8% of the isolates presented a multiple antibiotic resistance index (MARI) lower than 0.1, indicating that the risk of antibiotic resistance transmission of most of the Harveyi clade is low in mariculture systems in China. These results provide substantial data to support further studies on the identification and genetic and metabolic diversity of Harveyi clade isolates in mariculture systems in China.

Heterologous expression of ZmNF-YA12 confers tolerance to drought and salt stress in Arabidopsis - Tongtong Zhang; Dengyu Zheng; Chun Zhang; Zhongyi Wu; Rong Yu; Zhongbao Zhang (Plant Biotechnology Reports, 2022)

Antimicrobial Resistance and Genotype Characteristics of Vibrio scophthalmi Isolated from Diseased Mariculture Fish Intestines With Typical Inter-Annual Variability - Yongxiang Yu; Xiao Liu; Yingeng Wang; Meijie Liao; Miaomiao Tang; Xiaojun Rong; Chunyuan Wang; Bin Li; Zheng Zhang (Frontiers in Marine Science, 2022)
As an intestinal organism settled long-term within the gut of marine fish, Vibrio scophthalmi is a potential object for the bacterium genetic variation and adaptation research. The genetic diversity, antimicrobial resistance phenotype, and genotype of 33 V. scophthalmi isolated from diseased marine fish intestines between 2002 and 2020 were evaluated. The results showed that all isolates were frequently resistant to penicillins, cephalosporins, aminoglycosides, and macrolides and displayed multidrug-resistant (MDR) phenotype in vitro . Thirty percent of isolates were resistant to more than 20 different drugs. The average insensitive (resistant and intermediate) rate of V. scophthalmi isolates was 49.5%~81.8% between 2002 and 2020, but the t-test revealed that there was no significant difference in the drug-resistance rate of V. scophthalmi isolates with typical interannual variability. Eleven antimicrobial resistance genes ( strB , strA , ant(3 ˝)-I , mphA , blaPSE , qnrS , tetC , tetE , tetM , tetS , and int1 ) were detected in these isolates, but the antimicrobial resistance phenotypes and genotypes of these isolates were not consistent. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) analysis indicated that 33 isolates could be divided into two clusters (G1 and G3) and two single isolates (G2 and G4), and the G2 cluster was isolated from South Sea C. undulates with typical geographical species differences. There was no significant correlation between the drug susceptibility and the genetic types of V. scophthalmi isolates. The results reveal the mismatch phenomenon between antimicrobial resistance and genotype of inherent V. scophthalmi in the marine fish intestines, and the antimicrobial susceptibility isolates might be a potential risk source for storage and transmission of resistance genes.

Factors Influencing Alzheimer’s Disease Risk: Whether and How They are Related to the APOE Genotype - Rong Zhang; Xiaojiao Xu; Hang Yu; Xiaolan Xu; Manli Wang; Weidong Le (Neuroscience Bulletin, 2022)
Alzheimer's disease (AD) is the most prevalent neurodegenerative disease featuring progressive cognitive impairment. Although the etiology of late-onset AD remains unclear, the close association of AD with apolipoprotein E (APOE), a gene that mainly regulates lipid metabolism, has been firmly established and may shed light on the exploration of AD pathogenesis and therapy. However, various confounding factors interfere with the APOE -related AD risk, raising questions about our comprehension of the clinical findings concerning APOE . In this review, we summarize the most debated factors interacting with the APOE genotype and AD pathogenesis, depict the extent to which these factors relate to APOE -dependent AD risk, and discuss the possible underlying mechanisms.

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

Effect of biochar on transformation of dissolved organic matter and DTPA-extractable Cu and Cd during sediment composting - Meihua Zhao; Caiyuan Cai; Zhen Yu; Hongwei Rong; Chaosheng Zhang; Shungui Zhou (Environmental Science and Pollution Research, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

A new prenylated 3-benzoxepin derivative with anti-influenza A virus activity from Elsholtzia penduliflora - Lu Zhang; Linyao Yang; Rong-Tao Li; Fei Yu; Jindong Zhong (Natural Product Research, 2022)

Non-vernalization requirement in Chinese kale caused by loss of BoFLC and low expressions of its paralogs - Qiwei Tang; Hanhui Kuang; Changchun Yu; Guanghui An; Rong Tao; Weiyi Zhang; Yue Jia (Theoretical and Applied Genetics, 2022)
Key message We identified the loss of BoFLC gene as the cause of non-vernalization requirement in B. oleracea . Our developed codominant marker of BoFLC gene can be used for breeding program of B. oleracea crops . Abstract Many species of the Brassicaceae family, including some Brassica crops, require vernalization to avoid pre-winter flowering. Vernalization is an unfavorable trait for Chinese kale ( Brassica oleracea var. chinensis Lei ), a stem vegetable, and therefore it has been lost during its domestication/breeding process. To reveal the genetics of vernalization variation, we constructed an F 2 population through crossing a Chinese kale (a non-vernalization crop) with a kale (a vernalization crop). Using bulked segregant analysis (BSA) and RNA-seq, we identified one major quantitative trait locus (QTL) controlling vernalization and fine-mapped it to a region spanning 80 kb. Synteny analysis and PCR-based sequencing results revealed that compared to that of the kale parent, the candidate region of the Chinese kale parent lost a 9,325-bp fragment containing FLC homolog ( BoFLC ). In addition to the BoFLC gene, there are four other FLC homologs in the genome of B. oleracea , including Bo3g005470 , Bo3g024250 , Bo9g173370, and Bo9g173400 . The qPCR analysis showed that the BoFLC had the highest expression among the five members of the FLC family. Considering the low expression levels of the four paralogs of BoFLC , we speculate that its paralogs cannot compensate the function of the lost BoFLC, therefore the presence/absence (PA) polymorphism of BoFLC determines the vernalization variation. Based on the PA polymorphism of BoFLC , we designed a codominant marker for the vernalization trait, which can be used for breeding programs of B. oleracea crops.

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Selenium Deficiency Causes Inflammatory Injury in the Bursa of Fabricius of Broiler Chickens by Activating the Toll-like Receptor Signaling Pathway - Yu Bai; Ruili Zhang; Qing Liu; Rong Guo; Guangxing Li; Bin Sun; Di Zhang; Yang Chen; Xiaodan Huang (Biological Trace Element Research, 2022)

Overexpression of IbMPK3 increases low-temperature tolerance in transgenic sweetpotato - Rong Jin; Ho Soo Kim; Tao Yu; Ming Liu; Wenhui Yu; Peng Zhao; Aijun Zhang; Qiangqiang Zhang; Yaju Liu; Qinghe Cao; Sang-Soo Kwak; Zhonghou Tang (Plant Biotechnology Reports, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Effect of water level on dynamic compaction in silty ground of Yellow River alluvial plain - Kai Yao; Yu Rong; Zhanyong Yao; Changyuan Shi; Chenjun Yang; Luchuan Chen; Baoshuo Zhang; Hongguang Jiang (Arabian Journal of Geosciences, 2022)

On the Second-Year Warming in Late 2019 over the Tropical Pacific and Its Attribution to an Indian Ocean Dipole Event - Licheng Feng; Fei Liu; Rong-Hua Zhang; Xue Han; Bo Yu; Chuan Gao (Advances in Atmospheric Sciences, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Function identification of miR394 in tomato resistance to Phytophthora infestans - Yuan-Yuan Zhang; Yu-Hui Hong; Ya-Rong Liu; Jun Cui; Yu-Shi Luan (Plant Cell Reports, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

The effectiveness of extended binding affinity of prophage lysin PlyARI against Streptococcus suis infection - Yuyi Xiao; Rong Chen; Min Li; Zitai Qi; Yanfei Yu; Zihao Pan; Huochun Yao; Zhixin Feng; Wei Zhang (Archives of Microbiology, 2021)

A new atypical short‐chain dehydrogenase is required for interfungal combat and conidiation in Trichoderma guizhouense - Hong Zhu; Jian Zhang; Qi Gao; Guan Pang; Tingting Sun; Rong Li; Zhenzhong Yu; Qirong Shen (Environmental Microbiology, 2021)
Summary Hypocrealean Trichoderma are the most extensively studied facultative mycoparasites against phytopathogenic fungi. Aerial hyphae of Trichoderma guizhouense can rapidly proliferate over Fusarium oxysporum hyphae, cause sporadic cell death and arrest the growth of the host. The results of the present study demonstrated that a unique short‐chain dehydrogenase/reductase (SDR), designated as TgSDR1, was expressed at a high level in T . guizhouense challenged by the hosts. Similar to other SDRs family members, the TgSDR1 protein contains a cofactor‐binding motif and a catalytic site. The subcellular localization assay revealed that the TgSDR1::GFP fusion protein translocated to lipid droplets in mycelia and conidia. The data obtained using reverse genetic approach indicated that TgSDR1 is associated with antifungal ability, plays an important role in providing reducing equivalents in the form of NADPH and regulates the amino sugar and nucleotide sugar metabolism in T . guizhouense upon encountering a host. Moreover, the TgSDR1 deletion mutant was defective in conidiation. Thus, TgSDR1 functions as a key metabolic enzyme in T . guizhouense to regulate mycotrophic interactions, defence against other fungi, such as F . oxysporum , and conidiation.

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Reconstruction method of irregular seismic data with adaptive thresholds based on different sparse transform bases - Hu Zhao; Tun Yang; Yu-Dong Ni; Xing-Gang Liu; Yin-Po Xu; Yi-Lei Zhang; Guang-Rong Zhang (Applied Geophysics, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Mucor rongii sp. nov., a New Cold-Tolerant Species from China - Feirong Bai; Su Yao; Chengshan Cai; Tianci Zhang; Yu Wang; Wei Liu; Baowen Ma; Changyuan Rong; Chi Cheng (Current Microbiology, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Late Cretaceous granitic magmatism and Sn mineralization in the giant Yinyan porphyry tin deposit, South China: constraints from zircon and cassiterite U–Pb and molybdenite Re–Os geochronology - Peng-Cheng Hu; Wei-Guang Zhu; Hong Zhong; Rong-Qing Zhang; Xiao-Yu Zhao; Wei Mao (Mineralium Deposita, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Development of a Microfluidics-Based Quantitative Real-Time PCR to Rapidly Identify Photobacterium damselae subsp. damselae with Different Pathogenicity by Detecting the Presence of mcp or dly Gene - Zheng Zhang; Yongxiang Yu; Jing Chen; Yingeng Wang; Yong Jiang; Meijie Liao; Xiaojun Rong; Hao Zhang (Journal of Ocean University of China, 2021)

Chlamydia trachomatis induces autophagy by p62 in HeLa cell - Fuyan Wang; Hongbo Zhang; Xiaofang Lu; Quan Zhu; Tingting Shi; Rong Lu; Ping Yu; Lei Zhang; Yong Wang (World Journal of Microbiology and Biotechnology, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Infestation and distribution of gamasid mites on Himalayan field rat (Rattus nitidus) in Yunnan Province of Southwest China - Rong Xiang; Xian-Guo Guo; Cheng-Fu Zhao; Rong Fan; Ke-Yu Mao; Zhi-Wei Zhang; Xiao-Bin Huang (Biologia, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Heavy metal concentrations and associated health risks in edible tissues of marine nekton from the outer Pearl River Estuary, South China Sea - Chang-Ping Yang; Yan Liu; Bin-Bin Shan; Jing Xu; Wei Yu; Dian-Rong Sun; Zai-Wang Zhang (Environmental Science and Pollution Research, 2021)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Prenatal diagnosis and neonatal phenotype of a de novo microdeletion of 17p11.2p12 associated with Smith‒Magenis syndrome and external genital defects - Pingping Zhang; Yanmei Sun; Haishen Tian; Limin Rong; Fangna Wang; Xiaoping Yu; Yali Li; Jian Gao (Journal of Genetics, 2020)

The intestine of artificially bred larval turbot (Scophthalmus maximus) contains a stable core group of microbiota - Zheng Zhang; Yongxiang Yu; Yan Jiang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Qian Liu (Archives of Microbiology, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

The impact of particulate matter 2.5 on the risk of preeclampsia: an updated systematic review and meta-analysis - Hongbiao Yu; Yangxue Yin; Jiashuo Zhang; Rong Zhou (Environmental Science and Pollution Research, 2020)
There is increasing and inconsistent evidence of a linkage between maternal exposure to particulate matter 2.5 (PM2.5) and preeclampsia. Therefore, this study was conducted to investigate this relationship. Electronic databases including PubMed, Embase, Web of Science, and Cochrane Library were searched to identify articles published from inception to March 23, 2020, which showed a correlation between PM2.5 and preeclampsia. Finally, 9 of 523 initial studies were deemed eligible for inclusion. A random effect model was adopted to calculate the standardized odds ratio (OR) and 95% confidence interval (CI). Based on potential effect modification, subgroup analyses were further performed. Meta-analysis showed that maternal exposure to PM2.5 (per 10 μg/m 3 increment) elevated the risk of preeclampsia (OR = 1.32, 95% CI 1.10 to 1.58%). Compared with other pregnancy trimesters, the third trimester of pregnancy seems to be the period in which women are more susceptible to PM2.5. Significant effect modification of the correlation between PM2.5 exposure and preeclampsia according to multiple pregnancies, pregnancy stage, maternal-related disease history, and sample size was not observed. The results demonstrated that maternal exposure to PM2.5 may predispose pregnant women to develop preeclampsia, especially in the third trimester of pregnancy. Therefore, more efforts should be made to improve air quality to maintain the health of pregnant women.

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Ecological analysis of gamasid mites on the body surface of Norway rats (Rattus norvegicus) in Yunnan Province, Southwest China - Zhe Liu; Xian-Guo Guo; Rong Fan; Cheng-Fu Zhao; Ke-Yu Mao; Zhi-Wei Zhang; Yue Zhao (Biologia, 2020)

Ice sheet controls on fine-grained deposition at the southern Mendeleev Ridge since the penultimate interglacial - Liming Ye; Xiaoguo Yu; Weiyan Zhang; Rong Wang (Acta Oceanologica Sinica, 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Biochemical Toxicity and Potential Detoxification Mechanisms in Earthworms Eisenia fetida Exposed to Sulfamethazine and Copper - Hong Rong; Chengrun Wang; Haitao Liu; Min Zhang; Yueting Yuan; Yanjie Pu; Jin Huang; Jinyu Yu (Bulletin of Environmental Contamination and Toxicology, 2020)

Roles of Wind Stress and Subsurface Cold Water in the Second-Year Cooling of the 2017/18 La Niña Event - Licheng Feng; Rong-Hua Zhang; Bo Yu; Xue Han (Advances in Atmospheric Sciences, 2020)

A Novel Eyes Topical Drug Delivery System: CsA-LNC for the Treatment of DED - Anan Zhang; Rong Sun; Meixin Ran; Yaxin Deng; Ying Ge; Yunjing Zhu; Xiumei Tao; Lixia Shang; Jingxin Gou; Haibing He; Tian Yin; Yanjiao Wang; et al. (Pharmaceutical Research, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

High resolution UPLC-MS/MS method for simultaneous separation and determination of six flavonoids from semen cuscutae extract in rat plasma: application to comparative pharmacokinetic studies in normal and kidney-deficient rats - Wei Zhang; Zhi-Tian Fu; Yao Xie; Zhi-Wen Duan; Yu Wang; Rong-Hua Fan (Natural Product Research, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Effects of dietary proline on growth, physiology, biochemistry and TOR pathway-related gene expression in juvenile spotted drum Nibea diacanthus - Hua Rong; Fan Lin; Yunlong Zhang; Jun Yu; Chuanqi Yu; Haoran Zhang; Jude Juventus Aweya; Xiaobo Wen (Fisheries Science, 2020)

The effects of mesoscale oceanographic structures and ambient conditions on the catch of albacore tuna in the South Pacific longline fishery - Cheng Zhou; Pingguo He; Liuxiong Xu; Pascal Bach; Xuefang Wang; Rong Wan; Hao Tang; Yu Zhang (Fisheries Oceanography, 2020)
Albacore tuna ( Thunnus alalunga ) exhibit patchy concentrations associated with biological process at a wide range of spatial scales, resulting in variations in their catchability by fishing gears. Here, we investigated the association of catch variation for pelagic longlines in the South Pacific Ocean with oceanographic mesoscale structures (in horizontal dimension) and ambient conditions (in vertical dimension). The distribution of albacore tuna as indicated by catch per unit effort (CPUE) of longlines was significantly related to the presence of mesoscale structures, with higher CPUE found at locations closer to thermal fronts and with greater gradient magnitudes, as well as areas marked by peripheral contour line of the anticyclone indicated by Sea Surface Height Anomalies ~0.05 m. Surface mesoscale current velocity had the negative effect on the catch, probably as a result of decreased catchability by shoaling the hook depth. Vertical distribution of albacore in the survey region of South Pacific Ocean was hardly restricted by ambient temperature and oxygen concentration, though effect of ambient temperature was relevant and showed a negatively linear correlation with CPUE at the range of 20–24°C. On the contrary, albacore distribution was evidently dominated by the water depth and showed strong preference on water depth of 200 m, which was likely a representative feeding layer. The presence of prey resources and their accessibility by albacore revealed by mesoscale structures in the biological and physical processes, and catchability determined by the location of the baited hooks comprehensively contribute to the variability of catch.

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

Effect of different seasons (spring vs summer) on the microbiota diversity in the feces of dairy cows - Han Li; Rong Li; Huijun Chen; Jing Gao; Yu Wang; Yifeng Zhang; Zhili Qi (International Journal of Biometeorology, 2020)

Comparative profiling of roots small RNA expression and corresponding gene ontology and pathway analyses for low- and high-cadmium–accumulating genotypes of wheat in response to cadmium stress - Min Zhou; Shigang Zheng; Yunfang Li; Rong Liu; Lei Zhang; Yu Wu (Functional & Integrative Genomics, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Characterization and diagnostic marker development for Yr28-rga1 conferring stripe rust resistance in wheat - Shigang Zheng; Yu Wu; Min Zhou; Lian Zeng; Rong Liu; Yunfang Li; Zehou Liu; Chihong Zhang; Lu Lu; Lei Zhang (European Journal of Plant Pathology, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

Prenatal exposure to organophosphate pesticides, maternal paraoxonase 1 genotype, and childhood neurodevelopment at 24 months of age in Shandong, China - Yiwen Wang; Yan Zhang; Lin Ji; Yijun Zhou; Rong Shi; Michihiro Kamijima; Jun Ueyama; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Effects of dietary hydroxyproline on collagen metabolism, proline 4-hydroxylase activity, and expression of related gene in swim bladder of juvenile Nibea diacanthus - Hua Rong; Yunlong Zhang; Meilin Hao; Weiguang Zou; Jun Yu; Chuanqi Yu; Qinchao Shi; Xiaobo Wen (Fish Physiology and Biochemistry, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Effects of Different Preservation Methods on Physicochemical Property of Marine Pathogen Vibrio anguillarum - Yongxiang Yu; Zheng Zhang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Bin Li; Hao Zhang (Journal of Ocean University of China, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Impact of CYP2R1, CYP27A1 and CYP27B1 genetic polymorphisms controlling vitamin D metabolism on susceptibility to hepatitis C virus infection in a high-risk Chinese population - Jing-jing Yang; Hao-zhi Fan; Ting Tian; Meng-ping Wu; Chao-nan Xie; Peng Huang; Rong-bin Yu; Hong-Gang Yi; Yun Zhang; Jie Wang (Archives of Virology, 2019)

Synergistic effects of stromal cell-derived factor-1α and bone morphogenetic protein-2 treatment on odontogenic differentiation of human stem cells from apical papilla cultured in the VitroGel 3D system - Min Xiao; Jun Qiu; Rong Kuang; Beidi Zhang; Wei Wang; Qing Yu (Cell and Tissue Research, 2019)

Identification and mapping of a photoperiod response gene (QPpd.zafu-4A) on wild emmer wheat (Triticum turgidum L.) chromosome 4AL - Jinsheng Yu; Yunzheng Miao; Siqing Yang; Zhaobin Shi; Nana Miao; Mingquan Ding; Hua Zhang; Yurong Jiang; Junkang Rong (Euphytica, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Performance of CAMS-CSM in Simulating the Shortwave Cloud Radiative Effect over Global Stratus Cloud Regions: Baseline Evaluation and Sensitivity Test - Yihui Zhou; Yi Zhang; Xinyao Rong; Jian Li; Rucong Yu (Journal of Meteorological Research, 2019)

First report of isolation and complete genome of Vibrio rotiferianus strain SSVR1601 from cage‐cultured black rockfish ( Sebastes schlegelii ) associated with skin ulcer - Zheng Zhang; Yong‐xiang Yu; Yong Jiang; Yin‐geng Wang; Mei‐jie Liao; Xiao‐jun Rong; Kai Wang; Hao Zhang; Jing Chen (Journal of Fish Diseases, 2019)
Vibrio rotiferianus is an important marine pathogen of various aquatic organisms and can be found widely distributed in the marine environment. To further characterize this pathogen, the pathogenic properties and genome of V. rotiferianus SSVR1601 isolated from Sebastes schlegelii with skin ulcer were analysed. SSVR1601 was shown to be short rod‐shaped cell with a single polar flagellum. Different degrees of pathological changes in fish kidney, intestine, gills and liver were observed after SSVR1601 challenge. The SSVR1601 genome consists of two chromosomes and two plasmids with a total of 5,717,113 bp, 42.04%–44.93% GC content, 5,269 predicted CDSs, 134 tRNAs and 40 rRNAs. The common virulence factors including OMPs, haemolysin, flagellin, DNase, entF , algU , tcpI , acfB and rfaD were found in strain SSVR1601. Furthermore, factors responsible for iron uptake ( fur , fepC and ccmC ) and types II, IV and VI secretion systems were detected, which are likely responsible for the pathogenicity of SSVR1601. The antimicrobial resistance genes, bacA , tet34 and norM, were detected based on Antibiotic Resistance Genes Database. The phylogenetic analysis revealed SSVR1601 to be most closely related to V. rotiferianus strains CAIM577 and B64D1.

Phthalates in residential and agricultural soils from an electronic waste-polluted region in South China: distribution, compositional profile and sources - Shao-hui Zhang; Ai-jing Guo; Tong-tong Fan; Rong Zhang; Yu-jie Niu (Environmental Science and Pollution Research, 2019)

Interannual Salinity Variability in the Tropical Pacific in CMIP5 Simulations - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Peng Yu (Advances in Atmospheric Sciences, 2019)

Comparative analysis of root transcriptome profiles between low- and high-cadmium-accumulating genotypes of wheat in response to cadmium stress - Min Zhou; Shigang Zheng; Rong Liu; Jing Lu; Lu Lu; Chihong Zhang; Zehou Liu; Congpei Luo; Lei Zhang; Yu Wu (Functional & Integrative Genomics, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Efficiency of maternal-fetal transfer of perfluoroalkyl and polyfluoroalkyl substances - Yiwen Wang; Wenchao Han; Caifeng Wang; Yijun Zhou; Rong Shi; Eva Cecilie Bonefeld-Jørgensen; Qian Yao; Tao Yuan; Yu Gao; Jun Zhang; Ying Tian (Environmental Science and Pollution Research, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Correction to: Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji‑Dong Ya; Zhi‑Xiang Yu; Yong-Qiong Yang; Shu‑Dong Zhang; Zhi‑Rong Zhang; Jie Cai; Jun‑Bo Yang; Wen‑Bin Yu (Conservation Genetics Resources, 2018)

Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji-Dong Ya; Zhi-Xiang Yu; Yan-Qiong Yang; Shu-Dong Zhang; Zhi-Rong Zhang; Jie Cai; Jun-Bo Yang; Wen-Bin Yu (Conservation Genetics Resources, 2018)

Formation of disinfection byproducts from sulfamethoxazole during sodium hypochlorite disinfection of marine culture water - Chuan Rong; Yanan Shao; Yinghui Wang; Yuanyuan Zhang; Kefu Yu (Environmental Science and Pollution Research, 2018)

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Diversity of herbaceous plants and bacterial communities regulates soil resistome across forest biomes - Hang‐Wei Hu; Jun‐Tao Wang; Brajesh K. Singh; Yu‐Rong Liu; Yong‐Liang Chen; Yu‐Jing Zhang; Ji‐Zheng He (Environmental Microbiology, 2018)
Summary Antibiotic resistance is ancient and prevalent in natural ecosystems and evolved long before the utilization of synthetic antibiotics started, but factors influencing the large‐scale distribution patterns of natural antibiotic resistance genes (ARGs) remain largely unknown. Here, a large‐scale investigation over 4000 km was performed to profile soil ARGs, plant communities and bacterial communities from 300 quadrats across five forest biomes with minimal human impact. We detected diverse and abundant ARGs in forests, including over 160 genes conferring resistance to eight major categories of antibiotics. The diversity of ARGs was strongly and positively correlated with the diversity of bacteria, herbaceous plants and mobile genetic elements (MGEs). The ARG composition was strongly correlated with the taxonomic structure of bacteria and herbs. Consistent with this strong correlation, structural equation modelling demonstrated that the positive effects of bacterial and herb communities on ARG patterns were maintained even when simultaneously accounting for multiple drivers (climate, spatial predictors and edaphic factors). These findings suggest a paradigm that the interactions between aboveground and belowground communities shape the large‐scale distribution of soil resistomes, providing new knowledge for tackling the emerging environmental antibiotic resistance.

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Polybrominated diphenyl ethers in cord blood and perinatal outcomes from Laizhou Wan Birth Cohort, China - Limei Chen; Caifeng Wang; Yan Zhang; Yijun Zhou; Rong Shi; Chang Cui; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Effects of simvastatin on the function of splenic CD4+ and CD8+ T cells in sepsis mice - Bingbing Kong; Xiaofeng Wang; Wenping Yang; Xin Zhao; Rong Zhang; Yu Wang (Immunologic Research, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

The Effect of Bisphenol A on Growth, Morphology, Lipid Peroxidation, Antioxidant Enzyme Activity, and PS II in Cylindrospermopsis raciborskii and Scenedesmus quadricauda - Rong Xiang; Junqiong Shi; Yi Yu; Hongbo Zhang; Congcong Dong; Yanjun Yang; Zhongxing Wu (Archives of Environmental Contamination and Toxicology, 2018)

Genetic dissection and validation of candidate genes for flag leaf size in rice (Oryza sativa L.) - Xinxin Tang; Rong Gong; Wenqiang Sun; Chaopu Zhang; Sibin Yu (Theoretical and Applied Genetics, 2018)

Detrital apatite fission track constraints on Cenozoic tectonic evolution of the northeastern Qinghai-Tibet Plateau, China: Evidence from Cenozoic strata in Lulehe section, Northern Qaidam Basin - Ding-ding Du; Cheng-jun Zhang; Muhammad Saleem Mughal; Xiao-yu Wang; Dembele Blaise; Jun-ping Gao; Yuan Ma; Xin-rong Luo (Journal of Mountain Science, 2018)

EZH2 promotes cell proliferation by regulating the expression of RUNX3 in laryngeal carcinoma - Rong Lian; Huimin Ma; Zhiyan Wu; Guozheng Zhang; Lei Jiao; Wenjie Miao; Qianqian Jin; Ruixue Li; Ping Chen; Haixu Shi; Wenfa Yu (Molecular and Cellular Biochemistry, 2018)

Effect of spatial variability of engineering properties on stability of a CSMC embankment - Rong-Jun Zhang; Mohammed Shareef M. S. Hasan; Jun-Jie Zheng; Yu-Shi Cheng (Marine Georesources & Geotechnology, 2018)

Exploration of the formation mechanism and source attribution of ambient ozone in Chongqing with an observation-based model - Rong Su; KeDing Lu; JiaYan Yu; ZhaoFeng Tan; MeiQing Jiang; Jing Li; ShaoDong Xie; YuSheng Wu; LiMin Zeng; ChongZhi Zhai; YuanHang Zhang (Science China Earth Sciences, 2018)

β-Arrestin-1 deficiency ameliorates renal interstitial fibrosis by blocking Wnt1/β-catenin signaling in mice - Huiyan Xu; Quanxin Li; Jiang Liu; Jiaqing Zhu; Liang Li; Ziying Wang; Yan Zhang; Yu Sun; Jinpeng Sun; Rong Wang; Fan Yi (Journal of Molecular Medicine, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Injectable Sustained-Release Depots of PLGA Microspheres for Insoluble Drugs Prepared by hot-Melt Extrusion - Yuting Guo; Yunning Yang; Luying He; Rong Sun; Chenguang Pu; Bin Xie; Haibing He; Yu Zhang; Tian Yin; Yanjiao Wang; Xing Tang (Pharmaceutical Research, 2017)

Erratum to: Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Glucocorticoid-Potentiated Spinal Microglia Activation Contributes to Preoperative Anxiety-Induced Postoperative Hyperalgesia - Rao Sun; Zhibin Zhao; Jiying Feng; Jinhua Bo; Hui Rong; Yishan Lei; Cui’e Lu; Xiaobao Zhang; Bailing Hou; Yu’e Sun; Yue Liu; Zhengliang Ma; et al. (Molecular Neurobiology, 2017)

Sex-specific nonlinear associations between serum lipids and different domains of cognitive function in middle to older age individuals - Yanhui Lu; Yu An; Huanling Yu; Fengyuan Che; Xiaona Zhang; Hongguo Rong; Yuandi Xi; Rong Xiao (Metabolic Brain Disease, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Zebrafish phosvitin-derived peptide Pt5 inhibits melanogenesis via cAMP pathway - Yuan-Yuan Liu; Xiu-Rong Su; Shou-Sheng Liu; Shuang-Shuang Yang; Cheng-Yan Jiang; Yu Zhang; Shicui Zhang (Fish Physiology and Biochemistry, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Isolation, chemical characterization, and immunomodulatory activity of naturally acetylated hemicelluloses from bamboo shavings - Ju-qing Huang; Rui-ting Qi; Mei-rong Pang; Cong Liu; Guang-yu Li; Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Evaluating the contribution of Yr genes to stripe rust resistance breeding through marker-assisted detection in wheat - Shigang Zheng; Yunfang Li; Lu Lu; Zehou Liu; Chihong Zhang; Donghui Ao; Lirong Li; Chunyan Zhang; Rong Liu; Congpei Luo; Yu Wu; Lei Zhang (Euphytica, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Plasma Oxytocin and Arginine-Vasopressin Levels in Children with Autism Spectrum Disorder in China: Associations with Symptoms - Hong-Feng Zhang; Yu-Chuan Dai; Jing Wu; Mei-Xiang Jia; Ji-Shui Zhang; Xiao-Jing Shou; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Combinatorial anticancer effects of curcumin and sorafenib towards thyroid cancer cells via PI3K/Akt and ERK pathways - Junjia Zhang; Jichun Yu; Rong Xie; Wanzhi Chen; Yunxia Lv (Natural Product Research, 2016)

Strawberry MOTHER OF FT AND TFL1 regulates seed germination and post-germination growth through integrating GA and ABA signaling in Arabidopsis - Yang Hu; Yu-Rong Gao; Wei Wei; Kai Zhang; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Steroidobacter flavus sp. nov., a microcystin-degrading Gammaproteobacterium isolated from soil - Zhi-Lian Gong; Chang-Feng Zhang; Rong Jin; Yu-Qin Zhang (Antonie van Leeuwenhoek, 2016)

Long-Acting Phospholipid Gel of Exenatide for Long-Term Therapy of Type II Diabetes - Mei Hu; Yu Zhang; Nanxi Xiang; Ying Zhong; Tao Gong; Zhi-Rong Zhang; Yao Fu (Pharmaceutical Research, 2016)

Evaluation of the major royal jelly proteins as an alternative to fetal bovine serum in culturing human cell lines - Di Chen; Xiao-xuan Xin; Hao-cheng Qian; Zhang-yin Yu; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Prenatal low-level mercury exposure and infant neurodevelopment at 12 months in rural northern China - Yi Hu; Limei Chen; Caifeng Wang; Yijun Zhou; Yan Zhang; Yiwen Wang; Rong Shi; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2016)

Bacterial community dissimilarity between the surface and subsurface soils equals horizontal differences over several kilometers in the western Tibetan Plateau - Haiyan Chu; Huaibo Sun; Binu M. Tripathi; Jonathan M. Adams; Rong Huang; Yangjian Zhang; Yu Shi (Environmental Microbiology, 2016)
Summary Many studies have investigated patterns in the near‐surface soil microbial community over large spatial scales. However, less is known about variation in subsurface (15–30 cm of depth) microbial communities. Here we studied depth profiles of microbial communities in high‐elevation soils from Tibet. The relative abundance of Acidobacteria, Chloroflexi and Alphaproteobacteria was higher in near‐surface layers, while the relative abundance of Actinobacteria, Gemmatimonadetes and Betaproteobacteria was higher in the subsurface samples. The microbial community structure was distinct between the surface and subsurface soil layers, strongly correlating with variation in total carbon (TC) and carbon to nitrogen ratio (C/N). The differences in the microbial community between the layers were about the same as the horizontal differences between sites separated by many kilometers. Overall, we found that TC and C/N were the best predictors for both surface and subsurface microbial community distribution. Exploration of the relative contribution of distance and environmental variables to community composition suggests that the contemporary environment is the primary driver of microbial distribution in this region. Reflecting niche conservatism in evolution, the microbial communities in each soil site and layer tended to be more phylogenetically clustered than expected by chance, and surface soil layer samples were more likely to be clustered than subsurface samples.

Bridge life cycle assessment with data uncertainty - Yu-Rong Zhang; Wen-Jie Wu; Yuan-Feng Wang (The International Journal of Life Cycle Assessment, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Distribution and contamination assessment of heavy metals in soils from tidal flat, oil exploitation zone and restored wetland in the Yellow River Estuary - Xinying Yao; Rong Xiao; Ziwen Ma; Ying Xie; Mingxiang Zhang; Feihai Yu (Wetlands, 2016)

Isolation and characterization of the marine algicidal bacterium Pseudoalteromonas S1 against the harmful alga Akashiwo sanguinea - Hong-Ye Sun; Yu Zhang; Hui-Rong Chen; Chang-Xing Hu; Hui Li; Zhang-Li Hu (Marine Biology, 2016)

Heavy metal distribution in different soil aggregate size classes from restored brackish marsh, oil exploitation zone, and tidal mud flat of the Yellow River Delta - Rong Xiao; Mingxiang Zhang; Xinying Yao; Ziwen Ma; Feihai Yu; Junhong Bai (Journal of Soils and Sediments, 2016)

Selenium and Iodine Levels in Subjects with Kashin-Beck Disease: a Meta-analysis - Lei Yang; Guang-hui Zhao; Fang-fang Yu; Rong-qiang Zhang; Xiong Guo (Biological Trace Element Research, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Assessment of interannual sea surface salinity variability and its effects on the barrier layer in the equatorial Pacific using BNU-ESM - Hai Zhi; Rong-Hua Zhang; Fei Zheng; Pengfei Lin; Lanning Wang; Peng Yu (Advances in Atmospheric Sciences, 2016)

Effect of long-term industrial waste effluent pollution on soil enzyme activities and bacterial community composition - Gangavarapu Subrahmanyam; Ju-Pei Shen; Yu-Rong Liu; Gattupalli Archana; Li-Mei Zhang (Environmental Monitoring and Assessment, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Isolation, structural analysis, and expression characteristics of the maize TIFY gene family - Zhongbao Zhang; Xianglong Li; Rong Yu; Meng Han; Zhongyi Wu (Molecular Genetics and Genomics, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

Adsorption of Cs from Water on Surface-Modified MCM-41 Mesosilicate - Kai Guo; Fengxiang Han; Zikri Arslan; Jacqueline McComb; Xinyu Mao; Rong Zhang; Sinha Sudarson; Hongtao Yu (Water, Air, & Soil Pollution, 2015)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

Selenium geochemical distribution in the environment and predicted human daily dietary intake in northeastern Qinghai, China - Dasong Yu; Dongli Liang; Lingming Lei; Rong Zhang; Xiaofeng Sun; Zhiqing Lin (Environmental Science and Pollution Research, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Clay mineral assemblages at IODP Site U1340 in the Bering Sea and their paleoclimatic significance - Qiang Zhang; MuHong Chen; JianGuo Liu; ZhaoJie Yu; LanLan Zhang; Rong Xiang (Science China Earth Sciences, 2015)

The impact of the cognition of landscape experience on tourist environmental conservation behaviors - Yu-ling Zhang; Jie Zhang; Hong-Lei Zhang; Shao-wen Cheng; Yong-rui Guo; Jin-hai Ma; Jing-rong Sun (Journal of Mountain Science, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Nitrate reutilization mechanisms in the tonoplast of two Brassica napus genotypes with different nitrogen use efficiency - Yongliang Han; Qiong Liao; Yin Yu; Haixing Song; Qiang Liu; Xiangmin Rong; Jidong Gu; Joe Eugene Lepo; Chunyun Guan; Zhenhua Zhang (Acta Physiologiae Plantarum, 2015)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Heavy metal and organic contaminants in mangrove ecosystems of China: a review - Zai-Wang Zhang; Xiang-Rong Xu; Yu-Xin Sun; Shen Yu; Yong-Shan Chen; Jia-Xi Peng (Environmental Science and Pollution Research, 2014)

Fasudil Hydrochloride Protects Neurons in Rat Hippocampal CA1 Region through Inhibiting GluR6–MLK3–JNKs Signal Pathway - Xiu-E Wei; Feng-Yu Zhang; Kai Wang; Qing-Xiu Zhang; Liang-Qun Rong (Cell Biochemistry and Biophysics, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Response of bacterial pdo1, nah, and C12O genes to aged soil PAH pollution in a coke factory area - Xue-Mei Han; Yu-Rong Liu; Yuan-Ming Zheng; Xiao-Xia Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Cloning and expression analysis on a homolog of spermatogonial stem-cell renewal factor in Fenneropenaeus chinensis - Rong Wen; Fuhua Li; Yusu Xie; Shihao Li; Chengsong Zhang; Kuijie Yu; Jianhai Xiang (Invertebrate Reproduction & Development, 2014)

Estimate of NOX production in the lightning channel based on three-dimensional lightning locating system - Rong Zhang; GuangShu Zhang; YaJun Li; YanHui Wang; Bin Wu; Hai Yu; YanXiu Liu (Science China Earth Sciences, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

An improved wind speed algorithm for “Jason-1” altimeter under tropical cyclone conditions - Bangyong Qin; Xuan Zhou; Honglei Zhang; Xiaofeng Yang; Rong Lu; Yang Yu; Lijian Shi (Acta Oceanologica Sinica, 2014)

Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Synthesis and anticonvulsant evaluation of some new 1,3,4,5-tetrahydro-6-alkoxy-2H-1-benzazepin-2-one derivatives - Rong-Bi Han; Yun-Peng Shao; Hui-Fan Wu; Duo Zhang; Feng-Yu Piao (Medicinal Chemistry Research, 2014)

Eudragit L/HPMCAS Blend Enteric-Coated Lansoprazole Pellets: Enhanced Drug Stability and Oral Bioavailability - Yu Fang; Guozheng Wang; Rong Zhang; Zhihua Liu; Zhenghua Liu; Xiaohui Wu; Deying Cao (AAPS PharmSciTech, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Auditory sexual difference in the large odorous frog Odorrana graminea - Wei-Rong Liu; Jun-Xian Shen; Yu-Jiao Zhang; Zhi-Min Xu; Zhi Qi; Mao-Qiang Xue (Journal of Comparative Physiology A, 2014)

Gene expression profiles in intracranial aneurysms - Lanbing Yu; Jinghan Fan; Shuo Wang; Dong Zhang; Rong Wang; Yuanli Zhao; Jizong Zhao (Neuroscience Bulletin, 2014)

AngiotensinII induces HuR shuttling by post-transcriptional regulated CyclinD1 in human mesangial cells - Yu Che; Liu Yi; Javed Akhtar; Chen Bing; Zhang Ruiyu; Wan Qiang; Wang Rong (Molecular Biology Reports, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Neuroprotective effects of flavonoids extracted from licorice on kainate-induced seizure in mice through their antioxidant properties - Ling-hui Zeng; Hua-dan Zhang; Cai-ju Xu; Yu-jia Bian; Xue-jiao Xu; Qiang-min Xie; Rong-hua Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Discovery of a novel esterase subfamily sharing an identified arm sequence (ArmEst) by gene-specific metagenomic PCR - Ao Zhang; Rong Zhao; Peng Jin; Lifang Ma; Xiaolong Xiong; Tian Xie; Xiaolin Pei; Li Yu; Xiaopu Yin; Qiuyan Wang (Biotechnology Letters, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Short-term effect of cultivation and crop rotation systems on soil quality indicators in a coastal newly reclaimed farming area - Rong-Jiang Yao; Jing-Song Yang; Tong-Juan Zhang; Peng Gao; Shi-Peng Yu; Xiang-Ping Wang (Journal of Soils and Sediments, 2013)

Screening for Chip-Processing Potato Line from Introgression of Wild Species’ Germplasms with Post-Harvest Storage and Chip Qualities - Qingxia Zhao; Baoxie Zhao; Qingquan Zhang; Bin Yu; Lixiang Cheng; Rong Jin; Yuping Wang; Junlian Zhang; Di Wang; Feng Zhang (American Journal of Potato Research, 2013)

Genome-Wide Phylogenetic Analysis of Stress-Activated Protein Kinase Genes in Rice (OsSAPKs) and Expression Profiling in Response to Xanthomonas oryzae pv. oryzicola Infection - Mei-Rong Xu; Li-Yu Huang; Fan Zhang; Ling-Hua Zhu; Yong-Li Zhou; Zhi-Kang Li (Plant Molecular Biology Reporter, 2013)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

A Novel Peptide Can Mimic Extracellular Fibrinogen-Binding Protein to Block the Activation of Complement System - Ya-ping Gao; Jie Dong; Xin Zhang; Yu Liu; Qiang Lu; Jian-nan Feng; Xiao-rong Tan; Guang Yang (Cell Biochemistry and Biophysics, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Curcumin inhibits the metastasis of K1 papillary thyroid cancer cells via modulating E-cadherin and matrix metalloproteinase-9 expression - Chi-Yu Zhang; Li Zhang; Hui-Xin Yu; Jian-Dong Bao; Rong-Rong Lu (Biotechnology Letters, 2013)

Bacterioplankton community structure in the Arctic waters as revealed by pyrosequencing of 16S rRNA genes - Yin-Xin Zeng; Fang Zhang; Jian-Feng He; Sang H. Lee; Zong-Yun Qiao; Yong Yu; Hui-Rong Li (Antonie van Leeuwenhoek, 2013)

Diversity of bacteria in surface ice of Austre Lovénbreen glacier, Svalbard - Yin-Xin Zeng; Ming Yan; Yong Yu; Hui-Rong Li; Jian-Feng He; Kun Sun; Fang Zhang (Archives of Microbiology, 2013)

The Implantable and Biodegradable PHBHHx 3D Scaffolds Loaded with Protein-Phospholipid Complex for Sustained Delivery of Proteins - Qiang Peng; Yong-Jie Yang; Ting Zhang; Cheng-Yu Wu; Qin Yang; Xun Sun; Tao Gong; Ling Zhang; Zhi-Rong Zhang (Pharmaceutical Research, 2013)

Effects of breeds and dietary protein levels on the growth performance, energy expenditure and expression of avUCP mRNA in chickens - Qihua Li; Zhiqiang Xu; L. Liu; Hongxin Yu; Hua Rong; Linli Tao; Xi Zhang; Xiaobo Chen; Dahai Gu; Yueyuan Fan; Xiaoqin Li; Changrong Ge; et al. (Molecular Biology Reports, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Lipoic acid attenuates the expression of adhesion molecules by increasing endothelial nitric-oxide synthase activity - Hong-Bo Jin; Yong-Bin Yang; Ying-Li Song; Yong-chun Zhang; Yu-Rong Li (Molecular Biology Reports, 2013)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

Protective roles of quercetin in acute myocardial ischemia and reperfusion injury in rats - Hong-Bo Jin; Yong-Bin Yang; Ying-Li Song; Yong-chun Zhang; Yu-Rong Li (Molecular Biology Reports, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Protective effect of whey protein hydrolysates against hydrogen peroxide-induced oxidative stress on PC12 cells - Qiu-Xiang Zhang; Yu-Fang Ling; Zhen Sun; Li Zhang; Hui-Xin Yu; Samuel Mburu Kamau; Rong-Rong Lu (Biotechnology Letters, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Synthesis and anticonvulsant activity of 8-alkoxy-5,6-dihydro-4H-benzo[f][1,2,4]triazolo[4,3-a]azepine derivatives - Wen-Bin Zhang; Rong-Bi Han; Wei Zhang; Ri-Shan Jiang; Feng-Yu Piao (Medicinal Chemistry Research, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Influence of education and working background on physicians’ knowledge of secondary prevention guidelines for coronary heart disease: results from a survey in China - Yan-jun Gong; Tao Hong; Jie Jiang; Rong-hui Yu; Yan Zhang; Zhao-ping Liu; Yong Huo (Journal of Zhejiang University-SCIENCE B, 2012)

Functional analysis of the HS185 regulatory element in the rice HSP70 promoter - Yu-Man Zhang; Yu-Mei Zheng; Na Xiao; Li-Na Wang; Yao Zhang; Rong-Xiang Fang; Xiao-Ying Chen (Molecular Biology Reports, 2012)

Mitochondrial Permeability Transition Induced by Different Concentrations of Zinc - Xiao-Rong Liu; Jia-Han Li; Yue Zhang; Yu-Shu Ge; Fang-Fang Tian; Jie Dai; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Dynamics of vegetation and soil carbon and nitrogen accumulation over 26 years under controlled grazing in a desert shrubland - Zhi-Yu Zhou; Feng-Rui Li; Shan-Ke Chen; Hong-Rong Zhang; Guangdi Li (Plant and Soil, 2011)

QTL mapping for test weight by using F 2:3 population in maize - JUN-QIANG DING; JIN-LIANG MA; CHUN-RONG ZHANG; HUA-FANG DONG; ZHANG-YING XI; ZONG-LIANG XIA; JIAN-YU WU (Journal of Genetics, 2011)

Biophysical Studies on the Interactions of a Classic Mitochondrial Uncoupler with Bovine Serum Albumin by Spectroscopic, Isothermal Titration Calorimetric and Molecular Modeling Methods - Yue Zhang; Jia-Han Li; Yu-Shu Ge; Xiao-Rong Liu; Feng-Lei Jiang; Yi Liu (Journal of Fluorescence, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

An AFLP-based survey of genetic diversity and relationships of major farmed cultivars and geographically isolated wild populations of Saccharina japonica (Phaeophyta) along the northwest coasts of the Pacific - Ti Feng Shan; Shao Jun Pang; Yu Rong Zhang; Irina M. Yakovleva; Anna V. Skriptsova (Journal of Applied Phycology, 2011)

Immunomodulative effects of mesenchymal stem cells derived from human embryonic stem cells in vivo and in vitro - Zhou Tan; Zhong-yuan Su; Rong-rong Wu; Bin Gu; Yu-kan Liu; Xiao-li Zhao; Ming Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

A mini review of MAR-binding proteins - Tian-Yun Wang; Zhong-Min Han; Yu-Rong Chai; Jun-He Zhang (Molecular Biology Reports, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

The complete mitogenome and phylogenetic analysis of Bombyx mandarina strain Qingzhou - Xiao-long Hu; Guang-li Cao; Ren-yu Xue; Xiao-jian Zheng; Xing Zhang; Hai-rong Duan; Cheng-liang Gong (Molecular Biology Reports, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Detection of expression of influenza virus receptors in tissues of BALB/c mice by histochemistry - Zhang-Yong Ning; Min-Yi Luo; Wen-Bao Qi; Bo Yu; Pei-Rong Jiao; Ming Liao (Veterinary Research Communications, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Differential global genomic changes in rice root in response to low-, middle-, and high-osmotic stresses - Ting-chen Ma; Rong-jun Chen; Rong-rong Yu; Han-lai Zeng; Duan-pin Zhang (Acta Physiologiae Plantarum, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Direct visualization of bacterial infection process in nematode hosts by an improved immunocytochemical method - Bao-Yu Tian; Chong-Rong Ke; Wei Huang; Ke-Qin Zhang; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Persistence and dissipation of synthetic pyrethroid pesticides in red soils from the Yangtze River Delta area - Xiao-zhi Gu; Gang-ya Zhang; Li Chen; Rong-ling Dai; Yuan-chun Yu (Environmental Geochemistry and Health, 2008)

Evaluation of FORS-D Analysis: A Comparison with the Statistically Significant Stem-loop Potential - Chi-Yu Zhang; Ji-Fu Wei; Jian-Sheng Wu; Wen-Rong Xu; Xiao Sun; Shao-Heng He (Biochemical Genetics, 2008)

Development and evaluation of immunoassay for zeranol in bovine urine - Yuan Liu; Cun-zhen Zhang; Xiang-yang Yu; Zhi-yong Zhang; Xiao Zhang; Rong-rong Liu; Xian-jin Liu; Zhen-ming Gong (Journal of Zhejiang University-SCIENCE B, 2007)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Dependent mechanism of Chinese prepositions processing in the brain: evidence from event-related potentials - Huan-Hai Fang; Rong-Ping Zhang; Huan-Fei Fang; Ming-Yang Gao; Min Zheng; Xiao-Yu Sun (Neuroscience Bulletin, 2007)

Characterizing and estimating rice brown spot disease severity using stepwise regression, principal component regression and partial least-square regression - Zhan-yu Liu; Jing-feng Huang; Jing-jing Shi; Rong-xiang Tao; Wan Zhou; Li-li Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Proteomic analysis of the serum in patients with idiopathic pulmonary arterial hypertension - Min Yu; Xing-xiang Wang; Fu-rong Zhang; Yun-peng Shang; Yu-xi Du; Hong-juan Chen; Jun-zhu Chen (Journal of Zhejiang University-SCIENCE B, 2007)

Berbamine induces apoptosis in human hepatoma cell line SMMC7721 by loss in mitochondrial transmembrane potential and caspase activation - Guan-yu Wang; Jia-wei Zhang; Qing-hua Lü; Rong-zhen Xu; Qing-hua Dong (Journal of Zhejiang University-SCIENCE B, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Mutation induced by ethylmethanesulphonate (EMS), in vitro screening for salt tolerance and plant regeneration of sweet potato (Ipomoea batatas L.) - Yu-Shi Luan; Juan Zhang; Xiao-Rong Gao; Li-Jia An (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Pharmacokinetics of three proton pump inhibitors in Chinese subjects in relation to the CYP2C19 genotype - Hai-Ling Qiao; Yu-Rong Hu; Xin Tian; Lin-Jing Jia; Na Gao; Li-Rong Zhang; Yu-Zhong Guo (European Journal of Clinical Pharmacology, 2006)

Inheritance of the Triple-spikelet Character in a Tibetan Landrace of Common Wheat - Wu-Yun Yang; Bao-Rong Lu; Xiao-Rong Hu; Yi Yu; Yong Zhang (Genetic Resources and Crop Evolution, 2005)

Comparative studies of Danxia landforms in China - Qi Deli; Yu Rong; Zhang Renshun; Ge Yunjian; Li Jialin (Journal of Geographical Sciences, 2005)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

Thermal effects of building’s external surfaces in city - Yi-ping Zhang; Yun-ling He; Yu-hong Liu; You-xin Ma; You-rong Li; Jun-xia Dou (Chinese Geographical Science, 2004)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)